Resin film, metal-clad laminate, and circuit board

By using a sandwich structure in the resin film, the liquid crystal polymer layer is sandwiched with an adhesive layer having a predetermined storage elastic modulus, the problem of large transmission loss in high-frequency signal transmission is solved, and the dimensional stability and simplification of the manufacturing process are improved.

CN113462300BActive Publication Date: 2025-03-04NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202110229743.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-02
Publication Date
2025-03-04
Estimated Expiration
2041-03-02

AI Technical Summary

Technical Problem

The prior art has a problem of large transmission loss in high-frequency signal transmission, and at the same time, the adhesiveness between the liquid crystal polymer layer and the metal foil is insufficient, and the bonding process between the polyimide layer and the liquid crystal polymer layer is complicated.

Method used

A resin film with a sandwich structure of the liquid crystal polymer layer having a predetermined storage elastic modulus is used to sandwich the liquid crystal polymer layer, and the liquid crystal polymer layer is sandwiched by the first and second adhesive layers respectively to optimize dielectric characteristics and dimensional stability.

Benefits of technology

It effectively reduces transmission losses in high-frequency signal transmission, improves dimensional stability, and simplifies manufacturing processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113462300B_ABST
    Figure CN113462300B_ABST
Patent Text Reader

Abstract

The present invention provides a resin film, a metal-clad laminate and a circuit substrate that can reduce transmission loss even in the transmission of high-frequency signals and have excellent dimensional stability. The resin film (A) includes: a liquid crystal polymer layer (L); a first adhesive layer (B1) laminated on one side of the liquid crystal polymer layer (L); and a second adhesive layer (B2) laminated on the side of the liquid crystal polymer layer (L) opposite to the first adhesive layer (B1). The storage elastic modulus of the first adhesive layer (B1) and the second adhesive layer (B2) at 50°C are independently 1800MPa or less, and the maximum value of the storage elastic modulus at 180°C to 260°C is 800MPa or less. The dielectric loss tangent of the entire resin film at 10GHz is preferably 0.005 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin film which is effectively used as a material for a circuit board, for example, and a metal-clad laminate and a circuit board using the same. Background Art

[0002] In recent years, with the progress of miniaturization, lightness and space saving of electronic devices, the demand for flexible printed circuits (FPCs) that are thin, light, flexible and have excellent durability even when bent repeatedly has increased. FPCs can be installed three-dimensionally and at high density even in a limited space, so their use is gradually expanding in wiring or cables, connectors and other parts of movable parts of electronic devices such as hard disk drives (HDDs), digital video disks (DVDs), and smart phones.

[0003] In addition to high density, the high performance of equipment is promoted, so it is also necessary to deal with the high frequency of transmission signals. When transmitting high-frequency signals, if the transmission loss in the transmission path is large, undesirable conditions such as loss of electrical signals or prolonged signal delay time will occur. Therefore, in the future, it will also be important to reduce transmission loss in FPC. In order to cope with high-frequency signal transmission, research has been conducted on using liquid crystal polymers with low hygroscopicity, low dielectric constant, and low dielectric loss tangent as FPC materials as dielectric layers.

[0004] Although liquid crystal polymer has excellent dielectric properties, there is room for improvement in thermal properties or dimensional stability. In order to improve these properties, a resin film having a liquid crystal polymer layer on both sides of a polyimide layer is proposed (for example, patent document 1). However, there is room for improvement in the adhesion between the liquid crystal polymer layer and the metal foil. In order to obtain sufficient adhesion, it is necessary to use a metal foil with a large surface roughness. In the case described above, there is a concern that the transmission loss becomes larger. In addition, a resin film having a polyimide layer on a liquid crystal polymer layer is proposed (for example, patent document 2). However, when bonding a polyimide film to a liquid crystal polymer film, it is necessary to utilize surface roughening performed by plasma treatment, and the manufacturing process becomes complicated, or in order to suppress the curling of the resin film, it is necessary to select a polyimide film and a liquid crystal polymer film with a small difference in thermal expansion coefficient, and there is a problem that the applicable materials are restricted.

[0005] [Prior art literature]

[0006] [Patent Document]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 2016-117281

[0008] [Patent Document 2] Japanese Patent Application Publication No. 2015-74157 Summary of the invention

[0009] [Problems to be solved by the invention]

[0010] An object of the present invention is to provide a resin film, a metal-clad laminate, and a circuit board which can reduce transmission loss even in transmission of high-frequency signals and have excellent dimensional stability.

[0011] [Technical means to solve the problem]

[0012] As a result of intensive studies, the present inventors have found that the above-mentioned problems can be solved by forming a resin film having a sandwich structure in which a liquid crystal polymer layer is sandwiched between adhesive layers having a predetermined storage elastic modulus, thereby completing the present invention.

[0013] The resin film of the present invention includes: a liquid crystal polymer layer; a first adhesive layer laminated on one side of the liquid crystal polymer layer; and a second adhesive layer laminated on the side of the liquid crystal polymer layer opposite to the first adhesive layer.

[0014] In the resin film of the present invention, the storage elastic modulus of the first adhesive layer and the second adhesive layer at 50° C. is independently 1800 MPa or less, and the maximum value of the storage elastic modulus at 180° C. to 260° C. is independently 800 MPa or less.

[0015] In the resin film of the present invention, the dielectric loss tangent of the entire resin film at 10 GHz can be 0.005 or less.

[0016] In the resin film of the present invention, the glass transition temperatures (Tg) of the first adhesive layer and the second adhesive layer may each be 180° C. or lower.

[0017] In the resin film of the present invention, the first adhesive layer and the second adhesive layer may contain polyimide as a resin component. In such a case, the polyimide may contain an acid anhydride residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component, and contain 50 mol % or more of a diamine residue derived from a diamine derived from a dimer acid in which both terminal carboxylic acid groups of a dimer acid are substituted with a primary aminomethyl group or an amino group, relative to all diamine residues.

[0018] The resin film of the present invention may have the following relationship when the thickness of the liquid crystal polymer layer is TL, the thickness of the first adhesive layer is TB1, and the thickness of the second adhesive layer is TB2.

[0019] 0.15≦(TB1+TB2) / (TL+TB1+TB2)≦0.70

[0020] The metal-clad laminate of the present invention comprises: a first single-sided metal-clad laminate having a first metal layer and a first insulating resin layer laminated on at least one side of the first metal layer;

[0021] a second single-sided metal-clad laminate having a second metal layer and a second insulating resin layer laminated on at least one side of the second metal layer; and

[0022] The intermediate resin layer is arranged so as to abut against the first insulating resin layer and the second insulating resin layer, and is laminated between the first single-sided metal-clad laminate and the second single-sided metal-clad laminate.

[0023] Furthermore, in the metal-clad laminate of the present invention, the intermediate resin layer includes any of the above-mentioned resin films.

[0024] In the metal-clad laminate of the present invention, the total thickness T1 of the first insulating resin layer, the intermediate resin layer and the second insulating resin layer can be in the range of 50μm to 500μm, and the ratio (T2 / T1) of the thickness T2 of the intermediate resin layer to the total thickness T1 can be in the range of 0.50 to 0.90.

[0025] In the metal-clad laminate of the present invention, the first insulating resin layer and the second insulating resin layer may have a multilayer structure formed by sequentially stacking a thermoplastic polyimide layer, a non-thermoplastic polyimide layer and a thermoplastic polyimide layer, and the intermediate resin layer may be disposed in contact with the two thermoplastic polyimide layers.

[0026] In the metal-clad laminate of the present invention, the non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer contains tetracarboxylic acid residues and diamine residues, and the content of diamine residues derived from the diamine compound represented by the following general formula (A1) may be 80 mol parts or more relative to 100 mol parts of all diamine residues.

[0027] [Chemistry 1]

[0028]

[0029] In formula (A1), the linking group Z represents a single bond or -COO-, Y independently represents a monovalent hydrocarbon group with 1 to 3 carbon atoms which may be substituted by a halogen atom or a phenyl group, or an alkoxy group with 1 to 3 carbon atoms or a perfluoroalkyl or alkenyl group with 1 to 3 carbon atoms, n represents an integer of 0 to 2, and p and q independently represent integers of 0 to 4.

[0030] The circuit substrate of the present invention comprises: a first circuit substrate having a first wiring layer and a first insulating resin layer laminated on at least one side of the first wiring layer;

[0031] a second circuit substrate including a second wiring layer and a second insulating resin layer laminated on at least one side of the second wiring layer; and

[0032] The intermediate resin layer is arranged so as to abut against the first insulating resin layer and the second insulating resin layer, and is laminated between the first circuit substrate and the second circuit substrate.

[0033] Furthermore, in the circuit board of the present invention, the intermediate resin layer includes any of the above-mentioned resin films.

[0034] [Effects of the Invention]

[0035] The resin film of the present invention has a sandwich structure in which a liquid crystal polymer layer is sandwiched by an adhesive layer having a predetermined storage elastic modulus, and thus has excellent dielectric properties and dimensional stability. Therefore, in a circuit substrate using the resin film of the present invention, transmission loss during high-frequency signal transmission can be reduced, and dimensional stability can be ensured.

[0036] In addition, the metal-clad laminate of the present invention has a structure in which two single-sided metal-clad laminates are bonded together via the resin film, so the thickness of the insulating resin layer can be increased, the transmission loss during high-frequency signal transmission can be reduced, and the dimensional stability is excellent.

[0037] Therefore, by using the resin film or the metal-clad laminate of the present invention, it is possible to cope with higher frequencies in circuit boards, and it is also possible to improve reliability and yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a schematic diagram showing the cross-sectional structure of a resin film according to one embodiment of the present invention.

[0039] Figure 2 It is a schematic diagram showing the structure of a metal-clad laminate according to one embodiment of the present invention.

[0040] Figure 3 This is a schematic cross-sectional view showing the structure of a metal-clad laminate according to a preferred embodiment of the present invention.

[0041] Figure 4 This is an explanatory diagram of a position measurement target used for measuring the dimensional change rate after etching.

[0042] Figure 5 This is an explanatory diagram of an evaluation sample used for measuring the dimensional change rate after etching.

[0043] Explanation of symbols

[0044] 100: Metal-clad laminate

[0045] 101: Metal layer

[0046] 110: Polyimide layer

[0047] 111: Non-thermoplastic polyimide layer

[0048] 112: Thermoplastic polyimide layer

[0049] 120: Adhesive layer

[0050] 130: Single-sided metal-clad laminate

[0051] A: Resin film

[0052] A': Adhesive layer

[0053] B1: First adhesive layer

[0054] B2: Second adhesive layer

[0055] C: Metal-clad laminate

[0056] C1: The first single-sided metal-clad laminate

[0057] C2: Second single-sided metal-clad laminate

[0058] L: Liquid crystal polymer layer

[0059] M1: First metal layer

[0060] M2: Second metal layer

[0061] P1: First insulating resin layer

[0062] P2: Second insulating resin layer

[0063] T1, T2, T3: Thickness DETAILED DESCRIPTION

[0064] Embodiments of the present invention will be described with reference to the accompanying drawings as appropriate.

[0065] [Resin film]

[0066] Figure 1 : is a schematic diagram showing the structure of a resin film A according to one embodiment of the present invention. The resin film A includes: a liquid crystal polymer layer L; a first adhesive layer B1 laminated on one side of the liquid crystal polymer layer L; and a second adhesive layer B2 laminated on the side of the liquid crystal polymer layer L opposite to the first adhesive layer B1. The resin film A has a sandwich structure in which the liquid crystal polymer layer L is sandwiched between the first adhesive layer B1 and the second adhesive layer B2.

[0067] [Liquid crystal polymer layer]

[0068] The liquid crystal polymer layer L can be any layer containing liquid crystal polymer as the main component of the resin component, preferably more than 70% by weight of the resin component, more preferably more than 90% by weight of the resin component, and most preferably all of the resin components. Furthermore, the so-called main component of the resin component refers to a component contained in excess of 50% by weight relative to the total resin component. Liquid crystal polymers have substantially no frequency dependence of dielectric properties and have very excellent dielectric properties, and also contribute to improved flame retardancy.

[0069] In the liquid crystal polymer layer L, in order to make the dielectric properties of the resin film A as a whole excellent, it is preferable to use a monomer whose relative dielectric constant at 10 GHz is preferably in the range of 2 to 3.5, more preferably in the range of 2.6 to 3.3, and whose dielectric loss tangent is preferably less than 0.003, more preferably less than 0.002.

[0070] The melting point of the liquid crystal polymer is, for example, preferably 280° C. or higher, more preferably 290° C. or higher, and still more preferably 300° C. or higher. If the melting point is lower than 280° C., the polymer may melt during the manufacturing process of electronic devices and the like, which may cause changes in characteristics.

[0071] The liquid crystal polymer is not particularly limited, but is preferably a liquid crystal polymer having a polyester structure such as a known thermotropic liquid crystal polyester or polyester amide derived from compounds classified into the following (1) to (4) and derivatives thereof.

[0072] (1) Aromatic or aliphatic dihydroxy compounds

[0073] (2) Aromatic or aliphatic dicarboxylic acids

[0074] (3) Aromatic hydroxycarboxylic acid

[0075] (4) Aromatic diamine, aromatic hydroxylamine or aromatic aminocarboxylic acid

[0076] As a representative example of a liquid crystal polymer obtained from these raw material compounds, a copolymer having a combination of two or more structural units selected from the following formulas (a) to (n), and a copolymer comprising any one of the structural units represented by formula (a) or formula (e), and in particular, a copolymer comprising the structural unit represented by formula (a) and the structural unit represented by formula (e) is more preferred. In addition, the more aromatic rings in the liquid crystal polymer, the more effects of improving dielectric properties and flame retardancy can be expected, so it is preferred to use a liquid crystal polymer comprising an aromatic dihydroxy compound as (1) and an aromatic dicarboxylic acid as (2).

[0077] [Chemistry 2]

[0078]

[0079] The liquid crystal polymer layer L constituting the resin film A may contain, as appropriate, for example, a plasticizer, other resin components such as epoxy resin, a hardener, a hardening accelerator, an organic filler, an inorganic filler, a coupling agent, a flame retardant, and the like as optional components.

[0080] A commercially available liquid crystal polymer film can be appropriately selected and used as the liquid crystal polymer layer L. For example, a film manufactured by Kuraray Co., Ltd. (trade name: Vecstar) or the like can be preferably used.

[0081] [First Adhesive Layer and Second Adhesive Layer]

[0082] The storage elastic modulus of the first adhesive layer B1 and the second adhesive layer B2 at 50°C is independently 1800 MPa or less, and the maximum value of the storage elastic modulus at 180°C to 260°C is independently 800 MPa or less, preferably within the range of 500 MPa or less. By setting such a storage elastic modulus, the internal stress during thermocompression bonding is relaxed and the dimensional stability after circuit processing is maintained, and warping is not easily generated even after the reflow process after circuit processing.

[0083] Furthermore, the first adhesive layer B1 and the second adhesive layer B2 may have the same or different structures such as thickness, physical properties, and materials, but preferably have the same structure.

[0084] In order to maintain the overall dielectric properties of the resin film A well, in the first adhesive layer B1 and the second adhesive layer B2, it is preferable to use, as monomers, a relative dielectric constant at 10 GHz preferably in the range of 2 to 3.5, more preferably in the range of 2 to 3, and a dielectric loss tangent preferably less than 0.003, more preferably less than 0.0025.

[0085] The glass transition temperature (Tg) of the first adhesive layer B1 and the second adhesive layer B2 is preferably below 180°C, more preferably below 160°C. By setting the Tg of the first adhesive layer B1 and the second adhesive layer B2 to below 180°C, thermocompression bonding at low temperature can be performed, thereby relieving the internal stress generated when laminating with a metal-clad laminate, etc., and suppressing the dimensional change after circuit processing. If the Tg of the first adhesive layer B1 and the second adhesive layer B2 exceeds 180°C, the thermocompression bonding temperature when the resin film A is interposed between the metal-clad laminate, etc., becomes high, which may damage the dimensional stability after circuit processing.

[0086] The first adhesive layer B1 and the second adhesive layer B2 are preferably polyimide layers containing polyimide as the main component of the resin component, preferably 70% by weight or more of the resin component, more preferably 90% by weight or more of the resin component, and most preferably all of the resin component. The main component of the resin component refers to a component contained in an amount exceeding 50% by weight relative to the total resin component.

[0087] In the case where the first adhesive layer B1 and the second adhesive layer B2 are polyimide layers, the polyimide constituting them preferably contains an anhydride residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component, and contains 50 mol% or more of diamine residues derived from a diamine derived from a dimer acid in which two terminal carboxylic acid groups of a dimer acid are substituted with a primary aminomethyl group or an amino group relative to all diamine residues. Hereinafter, the polyimide constituting the first adhesive layer B1 and the second adhesive layer B2 is sometimes referred to as an "adhesive polyimide". Furthermore, in the present invention, "tetracarboxylic acid residue" means a tetravalent group derived from tetracarboxylic dianhydride, and "diamine residue" means a divalent group derived from a diamine compound. When the tetracarboxylic anhydride and the diamine compound as raw materials are reacted in approximately equimolar amounts, the types and molar ratios of the tetracarboxylic acid residues and diamine residues contained in the polyimide can be made to roughly correspond to the types and molar ratios of the raw materials.

[0088] In the present invention, "polyimide" refers to a resin including a polymer having an imide group in its molecular structure, such as polyamideimide, polyetherimide, polyesterimide, polysiloxaneimide, and polybenzimidazoleimide, in addition to polyimide.

[0089] (anhydride)

[0090] Adhesive polyimide can use tetracarboxylic anhydride commonly used in thermoplastic polyimide as raw material without particular limitation, but preferably uses raw material containing 90 mol% or more of tetracarboxylic anhydride represented by the following general formula (1) and / or general formula (2) relative to all tetracarboxylic anhydride components. In other words, adhesive polyimide preferably contains 90 mol% or more of tetracarboxylic acid residues derived from tetracarboxylic anhydride represented by the following general formula (1) and / or general formula (2) relative to all tetracarboxylic acid residues. It is preferred that the coexistence of softness and heat resistance of adhesive polyimide is easily achieved by containing 90 mol% or more of tetracarboxylic acid residues derived from tetracarboxylic anhydride represented by the following general formula (1) and / or general formula (2) relative to all tetracarboxylic acid residues. If the total amount of tetracarboxylic acid residues derived from tetracarboxylic anhydride represented by the following general formula (1) and / or general formula (2) is less than 90 mol%, there is a tendency that the solvent solubility of adhesive polyimide is reduced.

[0091] [Chemistry 3]

[0092]

[0093] In the general formula (1), X represents a single bond or a divalent group selected from the following formula; in the general formula (2), the cyclic part represented by Y represents a cyclic saturated hydrocarbon group selected from a 4-membered ring, a 5-membered ring, a 6-membered ring, a 7-membered ring or an 8-membered ring.

[0094] [Chemistry 4]

[0095]

[0096] In the above formula, Z represents -C6H4-, -(CH2)n- or -CH2-CH(-OC(=O)-CH3)-CH2-, and n represents an integer of 1 to 20.

[0097] Examples of the tetracarboxylic anhydride represented by the general formula (1) include 3,3',4,4'-biphenyl tetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride (DSDA), 4,4'-oxydiphthalic anhydride (ODPA), 4,4'-(hexafluoroisopropylidene) diphthalic anhydride (D ... anhydride (6FDA), 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), p-phenylenebis(trimellitic acid monoester) anhydride (TAHQ), ethylene glycol bisanhydro trimellitate (TMEG), etc. Among these, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) is particularly preferred. When BTDA is used, the carbonyl group (ketone group) contributes to the adhesion, so the adhesion of the adhesive polyimide can be improved. In addition, when the ketone group present in the molecular skeleton of BTDA reacts with the amino group of the amino compound used for cross-linking formation described later to form a C=N bond, it is easy to show the effect of improving heat resistance. From such a viewpoint, it is preferable that the tetracarboxylic acid residue derived from BTDA is contained in an amount of preferably 50 mol % or more, more preferably 60 mol % or more, based on all the tetracarboxylic acid residues.

[0098] Examples of the tetracarboxylic anhydride represented by the general formula (2) include 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 1,2,4,5-cyclohexanetetracarboxylic dianhydride, 1,2,4,5-cycloheptanetetracarboxylic dianhydride, and 1,2,5,6-cyclooctanetetracarboxylic dianhydride.

[0099] The adhesive polyimide may contain a tetracarboxylic acid residue derived from an acid anhydride other than the tetracarboxylic acid anhydride represented by the general formula (1) and the general formula (2) within a range that does not impair the effect of the invention. Such a tetracarboxylic acid residue is not particularly limited, and examples thereof include pyromellitic acid dianhydride, 2,3',3,4'-biphenyltetracarboxylic acid dianhydride, 2,2',3,3'-benzophenonetetracarboxylic acid dianhydride or 2,3,3',4'-benzophenonetetracarboxylic acid dianhydride, 2,3',3,4'-diphenylethertetracarboxylic acid dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, 3,3",4,4"-p-terphenyltetracarboxylic acid dianhydride, 2,3,3",4"-p-terphenyltetracarboxylic acid dianhydride or 2,2",3,3"-p-terphenyltetracarboxylic acid dianhydride, 2,2-dicarboxyphenyl ether tetracarboxylic acid dianhydride. (2,3-dicarboxyphenyl)-propane dianhydride or 2,2-bis(3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride or bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)sulfone dianhydride or bis(3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride or 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,2,7,8-phenanthrene-tetracarboxylic dianhydride, 1,2,6,7-phenanthrene-tetracarboxylic dianhydride or 1,2,9,10-phenanthrene-tetracarboxylic dianhydride carboxylic acid dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)tetrafluoropropane dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic dianhydride, 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-(or 1,4,5,8-)tetrachloro A tetracarboxylic acid residue derived from an aromatic tetracarboxylic acid dianhydride such as naphthalene-1,4,5,8-(or 2,3,6,7-)tetracarboxylic dianhydride, 2,3,8,9-perylene-tetracarboxylic dianhydride, 3,4,9,10-perylene-tetracarboxylic dianhydride, 4,5,10,11-perylene-tetracarboxylic dianhydride or 5,6,11,12-perylene-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, or 4,4'-bis(2,3-dicarboxyphenoxy)diphenylmethane dianhydride.

[0100] (Diamine)

[0101] Adhesive polyimide can use the diamine compound commonly used in thermoplastic polyimide as raw material without particular limitation, but preferably uses the raw material of the diamine derived from dimer acid containing 50 mol % or more of the two terminal carboxylic acid groups of dimer acid replaced by primary aminomethyl or amino group relative to the whole diamine components. In other words, the adhesive polyimide preferably contains 50 mol % or more of the diamine residue derived from the diamine derived from dimer acid containing 50 mol % or more of the two terminal carboxylic acid groups of dimer acid replaced by primary aminomethyl or amino group relative to the whole diamine residue. By containing 50 mol % or more of the diamine residue derived from the diamine derived from dimer acid, the low dielectric constant / low dielectric loss tangent of the adhesive polyimide can be achieved, and the adhesion can be improved.

[0102] The diamine derived from dimer acid is a mixture containing trimer components or monomer components other than dimer diamine, and therefore it is preferably purified for use. Hereinafter, the substance obtained by purifying the diamine derived from dimer acid is sometimes referred to as a "dimer diamine composition". The dimer diamine composition is a purified product containing the following component (a) as a main component, and the amounts of components (b) and (c) are controlled.

[0103] (a) Dimer diamine

[0104] The dimer diamine of component (a) refers to a diamine in which the two terminal carboxylic acid groups (-COOH) of the dimer acid are substituted by primary aminomethyl groups (-CH2-NH2) or amino groups (-NH2). Dimer acid is a known dibasic acid obtained by intermolecular polymerization of unsaturated fatty acids. Its industrial production process has been roughly standardized in the industry, and it can be obtained by dimerizing unsaturated fatty acids with carbon numbers of 11 to 22 using clay catalysts, etc. Regarding industrially obtained dimer acid, the main component is a dibasic acid with carbon number 36 obtained by dimerizing unsaturated fatty acids with carbon number 18 such as oleic acid, linoleic acid, and linolenic acid, and contains any amount of monomer acid (carbon number 18), trimer acid (carbon number 54), and other polymerized fatty acids with carbon number 20 to 54, depending on the degree of purification. In addition, after the dimerization reaction, double bonds remain, but in the present invention, dimer acid also includes compounds that are further hydrogenated to reduce the degree of unsaturation. The dimer diamine of the component (a) can be defined as a diamine compound obtained by substituting the terminal carboxylic acid group of a dibasic acid compound having a carbon number in the range of 18 to 54, preferably in the range of 22 to 44, with a primary aminomethyl group or an amino group.

[0105] As a feature of dimer diamine, the characteristics of the skeleton derived from dimer acid can be given. That is, dimer diamine is a macromolecular aliphatic with a molecular weight of about 560 to 620, so the molar volume of the molecule can be increased, and the polar group of the polyimide can be relatively reduced. It is believed that the characteristics of such dimer diamine contribute to suppressing the reduction of the heat resistance of polyimide, and reducing the relative dielectric constant and dielectric loss tangent to improve dielectric properties. In addition, due to containing two freely movable hydrophobic chains of carbon numbers 7 to 9 and two chain aliphatic amino groups with a length close to carbon number 18, not only can flexibility be given to polyimide, but also polyimide can be set to an asymmetric chemical structure or a non-planar chemical structure, so it is believed that the low dielectric constant of polyimide can be achieved.

[0106] The dimer diamine composition preferably uses a dimer diamine whose content of the dimer diamine of the component (a) is increased to 96% by weight or more, preferably 97% by weight or more, and more preferably 98% by weight or more by a purification method such as molecular distillation. By setting the content of the dimer diamine of the component (a) to 96% by weight or more, the expansion of the molecular weight distribution of the polyimide can be suppressed. Furthermore, if technically achievable, it is optimal that the dimer diamine composition is entirely (100% by weight) composed of the dimer diamine of the component (a).

[0107] (b) a monoamine compound obtained by substituting the terminal carboxylic acid group of a monobasic acid compound having a carbon number in the range of 10 to 40 with a primary aminomethyl group or an amino group;

[0108] The monoacid compound having a carbon number in the range of 10 to 40 is a mixture of a monobasic unsaturated fatty acid having a carbon number in the range of 10 to 20 derived from a raw material of dimer acid and a monoacid compound having a carbon number in the range of 21 to 40, which is a byproduct when producing dimer acid. The monoamine compound is a compound obtained by substituting the terminal carboxylic acid group of these monoacid compounds with a primary aminomethyl group or an amino group.

[0109] The monoamine compound of component (b) is a component that suppresses the increase in molecular weight of polyimide. During the polymerization of polyamic acid or polyimide, the monofunctional amino group of the monoamine compound reacts with the terminal anhydride group of polyamic acid or polyimide, thereby sealing the terminal anhydride group and suppressing the increase in molecular weight of polyamic acid or polyimide.

[0110] (c) an amine compound obtained by substituting a terminal carboxylic acid group of a polyacid compound having a hydrocarbon group and having a carbon number in the range of 41 to 80 with a primary aminomethyl group or an amino group (except the dimer diamine);

[0111] The polybasic acid compound having a hydrocarbon group with a carbon number in the range of 41 to 80 is a polybasic acid compound having a carbon number in the range of 41 to 80, which is a byproduct when producing dimer acid, as a main component. In addition, it may also contain a polymerized fatty acid other than the dimer acid with a carbon number of 41 to 80. The amine compound is a compound obtained by replacing the terminal carboxylic acid group of these polybasic acid compounds with a primary aminomethyl group or an amino group.

[0112] The amine compound of component (c) is a component that promotes the increase of the molecular weight of polyimide. The trifunctional or higher amino group of the triamine body derived from trimer acid as the main component reacts with the terminal anhydride group of polyamic acid or polyimide to increase the molecular weight of polyimide sharply. In addition, the amine compound derived from the polymerized fatty acid other than the dimer acid having 41 to 80 carbon atoms also increases the molecular weight of polyimide and becomes the cause of gelation of polyamic acid or polyimide.

[0113] When each component is quantitatively determined by using gel permeation chromatography (GPC), in order to easily confirm the peak start, peak top and peak end of each component of the dimer diamine composition, a sample obtained by treating the dimer diamine composition with acetic anhydride and pyridine is used, and cyclohexanone is used as an internal standard substance. Using the sample prepared as described above, each component is quantitatively determined by the area percentage of the chromatogram of GPC. The peak start and peak end of each component are set to the minimum value of each peak curve, and the area percentage of the chromatogram can be calculated based on this.

[0114] In addition, the dimer diamine composition preferably contains the components (b) and (c) in an area percentage of a chromatogram obtained by GPC measurement of 4% or less, preferably less than 4%. By making the total of the components (b) and (c) 4% or less, the expansion of the molecular weight distribution of the polyimide can be suppressed.

[0115] In addition, the area percentage of the chromatogram of the component (b) is preferably 3% or less, more preferably 2% or less, and further preferably 1% or less. By setting it to such a range, the decrease in the molecular weight of the polyimide can be suppressed, and the range of the molar ratio of the tetracarboxylic anhydride component and the diamine component can be expanded. Furthermore, the component (b) may not be included in the dimer diamine composition.

[0116] In addition, the area percentage of the chromatogram of the component (c) is 2% or less, preferably 1.8% or less, and more preferably 1.5% or less. By setting it to such a range, the rapid increase of the molecular weight of the polyimide can be suppressed, and the increase of the dielectric loss tangent under the wide frequency of the resin film can be suppressed. Furthermore, the component (c) may not be included in the dimer diamine composition.

[0117] In addition, when the ratio (b / c) of the area percentage of the chromatogram of component (b) and component (c) is 1 or more, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably set to 0.97 or more and less than 1.0. By setting such a molar ratio, it is easier to control the molecular weight of the polyimide.

[0118] In addition, when the ratio (b / c) of the area percentage of the chromatogram of component (b) and component (c) is less than 1, the molar ratio of the tetracarboxylic anhydride component and the diamine component (tetracarboxylic anhydride component / diamine component) is preferably set to 0.97 or more and 1.1 or less. By setting such a molar ratio, it is easier to control the molecular weight of the polyimide.

[0119] As a diamine derived from dimer acid, a commercial product can be used, preferably for the purpose of reducing the components other than the dimer diamine of component (a), for example, it is preferred to purify component (a) to 96% by weight or more. As a purification method, there is no particular limitation, but it is suitable to be a known method such as distillation or precipitation purification. As a commercial product of a diamine derived from dimer acid, for example, PRIAMINE 1073 (trade name) manufactured by Croda Japan, PRIAMINE 1074 (trade name) manufactured by Croda Japan, PRIAMINE 1075 (trade name) manufactured by Croda Japan, etc.

[0120] The adhesive polyimide may contain a diamine residue derived from a diamine component other than the above. As such a diamine residue, for example, a diamine residue derived from a diamine compound represented by General Formula (B1) to General Formula (B7) is preferred.

[0121] [Chemistry 5]

[0122]

[0123] In formula (B1) to formula (B7), R1 independently represents a monovalent hydrocarbon group or alkoxy group having 1 to 6 carbon atoms, the linking group A independently represents a divalent group selected from -O-, -S-, -CO-, -SO-, -SO2-, -COO-, -CH2-, -C(CH3)2-, -NH- or -CONH-, and n1 independently represents an integer of 0 to 4. However, the part repeating with formula (B2) is removed from formula (B3), and the part repeating with formula (B4) is removed from formula (B5). Here, the so-called "independently" means that multiple linking groups A, multiple R1s or multiple n1s in one formula or two or more formulas in the formula (B1) to formula (B7) may be the same or different. Furthermore, in the formula (B1) to formula (B7), the hydrogen atoms in the two terminal amino groups may be substituted, for example, they may be -NR2R3 (here, R2 and R3 independently refer to any substituent such as an alkyl group).

[0124] The diamine represented by formula (B1) (hereinafter, sometimes referred to as "diamine (B1)") is an aromatic diamine having two benzene rings. It is believed that the diamine (B1) is in the meta position with the divalent linking group A through the amino group directly bonded to at least one benzene ring, and the degree of freedom of the polyimide molecular chain is increased and has high flexibility, which helps to improve the flexibility of the polyimide molecular chain. Therefore, by using diamine (B1), the thermoplasticity of the polyimide is improved. Here, as the linking group A, preferably -O-, -CH2-, -C(CH3)2-, -CO-, -SO2-, -S-.

[0125] Examples of the diamine (B1) include 3,3'-diaminodiphenylmethane, 3,3'-diaminodiphenylpropane, 3,3'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylpropane, 3,4'-diaminodiphenyl sulfide, 3,3'-diaminobenzophenone, and (3,3'-bisamino)diphenylamine.

[0126] The diamine represented by formula (B2) (hereinafter, sometimes referred to as "diamine (B2)") is an aromatic diamine having three benzene rings. It is believed that the diamine (B2) is in the meta position with the divalent linking group A through the amino group directly bonded to at least one benzene ring, and the degree of freedom of the polyimide molecular chain is increased and has high flexibility, which helps to improve the flexibility of the polyimide molecular chain. Therefore, by using diamine (B2), the thermoplasticity of the polyimide is improved. Here, as the linking group A, -O- is preferred.

[0127] As a diamine (B2), 1, 4- bis (3-aminophenoxy) benzene, 3- [4- (4-aminophenoxy) phenoxy] aniline, 3- [3- (4-aminophenoxy) phenoxy] aniline etc. are mentioned, for example.

[0128] The diamine represented by formula (B3) (hereinafter, sometimes referred to as "diamine (B3)") is an aromatic diamine having three benzene rings. It is believed that the diamine (B3) is in the meta position with two divalent linking groups A directly bonded to one benzene ring, and the degree of freedom of the polyimide molecular chain is increased and has high flexibility, which helps to improve the flexibility of the polyimide molecular chain. Therefore, by using diamine (B3), the thermoplasticity of the polyimide is improved. Here, as the linking group A, -O- is preferred.

[0129] Examples of the diamine (B3) include 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,3-bis(3-aminophenoxy)benzene (APB), 4,4'-[2-methyl-(1,3-phenylene)bisoxy]dianiline, 4,4'-[4-methyl-(1,3-phenylene)bisoxy]dianiline, and 4,4'-[5-methyl-(1,3-phenylene)bisoxy]dianiline.

[0130] The diamine represented by formula (B4) (hereinafter, sometimes referred to as "diamine (B4)") is an aromatic diamine having four benzene rings. It is believed that the diamine (B4) has high flexibility due to the amino group directly bonded to at least one benzene ring and the divalent linking group A being in the meta position, which helps to improve the flexibility of the polyimide molecular chain. Therefore, by using diamine (B4), the thermoplasticity of the polyimide is improved. Here, as the linking group A, preferably -O-, -CH2-, -C(CH3)2-, -SO2-, -CO-, -CONH-.

[0131] Examples of the diamine (B4) include bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]propane, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)]benzophenone, and bis[4,4′-(3-aminophenoxy)]benzanilide.

[0132] The diamine represented by formula (B5) (hereinafter, sometimes referred to as "diamine (B5)") is an aromatic diamine having four benzene rings. It is believed that the diamine (B5) is in the meta position with two divalent linking groups A directly bonded to at least one benzene ring, and the degree of freedom of the polyimide molecular chain is increased and has high flexibility, which helps to improve the flexibility of the polyimide molecular chain. Therefore, by using diamine (B5), the thermoplasticity of the polyimide is improved. Here, as the linking group A, -O- is preferred.

[0133] Examples of the diamine (B5) include 4-[3-[4-(4-aminophenoxy)phenoxy]phenoxy]aniline and 4,4′-[oxybis(3,1-phenyleneoxy)]dianiline.

[0134] The diamine represented by formula (B6) (hereinafter, sometimes referred to as "diamine (B6)") is an aromatic diamine having four benzene rings. It is believed that the diamine (B6) has high flexibility due to having at least two ether bonds, which helps to improve the flexibility of the polyimide molecular chain. Therefore, by using diamine (B6), the thermoplasticity of the polyimide is improved. Here, as the linking group A, preferably -C(CH3)2-, -O-, -SO2-, -CO-.

[0135] Examples of the diamine (B6) include 2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), bis[4-(4-aminophenoxy)phenyl]ether (BAPE), bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS), and bis[4-(4-aminophenoxy)phenyl]ketone (BAPK).

[0136] The diamine represented by formula (B7) (hereinafter, sometimes referred to as "diamine (B7)") is an aromatic diamine having four benzene rings. The diamine (B7) has a divalent linking group A with high flexibility on both sides of the diphenyl skeleton, and is therefore believed to contribute to the improvement of the flexibility of the polyimide molecular chain. Therefore, by using diamine (B7), the thermoplasticity of the polyimide is improved. Here, as the linking group A, -O- is preferred.

[0137] As a diamine (B7), bis[4-(3-aminophenoxy)]biphenyl, bis[4-(4-aminophenoxy)]biphenyl, etc. are mentioned, for example.

[0138] The adhesive polyimide preferably contains diamine residues derived from at least one diamine compound selected from diamines (B1) to (B7) in an amount preferably in the range of 1 mol% to 50 mol%, more preferably in the range of 5 mol% to 35 mol%, relative to all diamine residues. Since diamines (B1) to (B7) have a molecular structure having flexibility, by using at least one diamine compound selected from these in an amount within the above range, the flexibility of the polyimide molecular chain can be improved and thermoplasticity can be imparted.

[0139] The adhesive polyimide may further contain diamine residues other than those described above within a range not impairing the effects of the invention.

[0140] Adhesive polyimide can be manufactured by reacting the anhydride component and the diamine component in a solvent, and heating and ring-closing after generating polyamic acid. For example, the anhydride component and the diamine component are dissolved in an organic solvent in approximately equimolar amounts, and the polymerization reaction is carried out by stirring for 30 minutes to 24 hours at a temperature in the range of 0°C to 100°C, thereby obtaining a polyamic acid as a precursor of the polyimide. During the reaction, the reaction components are dissolved in a manner such that the generated precursor is in the range of 5% by weight to 50% by weight, preferably in the range of 10% by weight to 40% by weight in the organic solvent. Examples of the organic solvent used in the polymerization reaction include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, methylcyclohexane, dioxane, tetrahydrofuran, diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme), methanol, ethanol, benzyl alcohol, cresol, etc. These solvents may be used in combination of two or more, and aromatic hydrocarbons such as xylene and toluene may also be used in combination. The amount of the organic solvent used is not particularly limited, but is preferably adjusted so that the concentration of the polyamic acid solution obtained by the polymerization reaction becomes about 5% by weight to 50% by weight.

[0141] The synthesized polyamic acid is advantageously usually used as a reaction solvent solution, and can be concentrated, diluted or replaced with other organic solvents as needed. In addition, polyamic acid is usually excellent in solvent solubility, so it is advantageously used. The viscosity of the solution of polyamic acid is preferably within the range of 500mPa·s~100000mPa·s. If it deviates from the scope, it is easy to produce uneven thickness, stripes and other defects in the film when applying the coating operation using a coating machine etc.

[0142] The method for imidizing the polyamic acid to form the polyimide is not particularly limited, and for example, a heat treatment such as heating in the solvent at a temperature condition in the range of 80° C. to 400° C. for 1 to 24 hours can be suitably adopted. In addition, the temperature can be heated at a constant temperature condition, or the temperature can be changed in the middle of the process.

[0143] By selecting the types of the anhydride component and the diamine component in the adhesive polyimide, or the molar ratio of the two or more anhydride components or diamine components, physical properties such as dielectric properties, thermal expansion coefficient, tensile elastic modulus, and glass transition temperature can be controlled. In addition, when the adhesive polyimide has a plurality of structural units, they may exist in the form of blocks or randomly, but preferably exist randomly.

[0144] The weight average molecular weight of the adhesive polyimide is preferably in the range of 10,000 to 400,000, and more preferably in the range of 50,000 to 350,000. If the weight average molecular weight is less than 10,000, the strength of the film is reduced and the film tends to be brittle. On the other hand, if the weight average molecular weight exceeds 400,000, the viscosity is excessively increased, and defects such as uneven film thickness and streaks are easily generated during coating.

[0145] (Cross-linking formation of adhesive polyimide)

[0146] When the adhesive polyimide has a ketone group, a cross-linking agent having a functional group that undergoes a nucleophilic addition reaction with the ketone group is reacted to form a cross-linked structure. By forming a cross-linked structure, heat resistance can be improved. This polyimide having a cross-linked structure (hereinafter, sometimes referred to as "cross-linked polyimide") is an application example of the adhesive polyimide and becomes a preferred form.

[0147] As the crosslinking agent, for example, an amino compound having at least two primary amino groups as functional groups (hereinafter sometimes referred to as "crosslinking-forming amino compound") is preferably used. By reacting the ketone group of the adhesive polyimide with the amino group of the crosslinking-forming amino compound to form a C=N bond, a crosslinking structure can be formed. That is, the two primary amino groups in the amino compound function as functional groups that undergo a nucleophilic addition reaction with the ketone group.

[0148] As a preferred tetracarboxylic anhydride for forming an adhesive polyimide having a ketone group, for example, 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) can be cited, and as a diamine compound, for example, aromatic diamines such as 4,4'-bis(3-aminophenoxy)benzophenone (4,4'-bis(3-aminophenoxy)benzophenone, BABP) and 1,3-bis[4-(3-aminophenoxy)benzoyl]benzene (1,3-bis[4-(3-aminophenoxy)benzoyl]benzene, BABB) can be cited. For the purpose of forming a crosslinked structure, it is particularly preferred to allow an amino compound for crosslinking formation to act on the adhesive polyimide, and the adhesive polyimide contains preferably 50 mol% or more, more preferably 60 mol% or more of BTDA residues derived from BTDA relative to all tetracarboxylic acid residues. In addition, in the present invention, the so-called "BTDA residue" refers to a tetravalent group derived from BTDA.

[0149] As the amino compound for crosslinking formation, there can be exemplified: (I) dihydrazide compounds, (II) aromatic diamines, (III) aliphatic amines, etc. Among these, dihydrazide compounds are preferred. Aliphatic amines other than dihydrazide compounds are easy to form crosslinked structures even at room temperature, and there are concerns about the storage stability of the varnish. On the other hand, aromatic diamines need to be set to high temperature in order to form a crosslinked structure. As described above, when a dihydrazide compound is used, the storage stability of the varnish can be achieved while shortening the curing time. As the dihydrazide compound, for example, dihydrazide compounds such as oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, pimelic acid dihydrazide, suberic acid dihydrazide, azelaic acid dihydrazide, sebacic acid dihydrazide, dodecanedioic acid dihydrazide, maleic acid dihydrazide, fumaric acid dihydrazide, diglycolic acid dihydrazide, tartaric acid dihydrazide, malic acid dihydrazide, phthalic acid dihydrazide, isophthalic acid dihydrazide, terephthalic acid dihydrazide, 2,6-naphthoic acid dihydrazide, 4,4-diphenyl dihydrazide, 1,4-naphthoic acid dihydrazide, 2,6-pyridine dihydrazide, and itaconic acid dihydrazide are preferred. The above dihydrazide compounds may be used alone or in combination of two or more.

[0150] Furthermore, the amino compounds (I) dihydrazide compounds, (II) aromatic diamines, (III) aliphatic amines, etc. may be used in combination of two or more, for example, a combination of (I) and (II), a combination of (I) and (III), or a combination of (I) and (II) and (III).

[0151] In addition, from the viewpoint of making the network structure formed by crosslinking using the crosslinking amino compound denser, the molecular weight of the crosslinking amino compound used in the present invention (the weight average molecular weight when the crosslinking amino compound is an oligomer) is preferably 5,000 or less, more preferably 90 to 2,000, and further preferably 100 to 1,500. Among them, a crosslinking amino compound having a molecular weight of 100 to 1,000 is particularly preferred. If the molecular weight of the crosslinking amino compound is less than 90, one amino group of the crosslinking amino compound is limited to forming a C=N bond with the ketone group of the adhesive polyimide, and the surrounding of the remaining amino group becomes sterically bulky, so there is a tendency that the remaining amino group is not easy to form a C=N bond.

[0152] When the ketone group in the adhesive polyimide is cross-linked with the cross-linking amino compound, the cross-linking amino compound is added to the resin solution containing the adhesive polyimide to cause the ketone group in the adhesive polyimide to undergo a condensation reaction with the primary amino group of the cross-linking amino compound. The resin solution is cured by the condensation reaction to become a cured product. In the above case, the amount of the cross-linking amino compound added may be 0.004 mol to 1.5 mol, preferably 0.005 mol to 1.2 mol, more preferably 0.03 mol to 0.9 mol, and most preferably 0.04 mol to 0.6 mol of the primary amino group relative to 1 mol of the ketone group. Regarding the addition amount of the cross-linking amino compound such as less than 0.004 mol of the total primary amino group relative to 1 mol of the keto group, since the cross-linking by the cross-linking amino compound is insufficient, there is a tendency that the heat resistance after curing is difficult to exhibit. If the addition amount of the cross-linking amino compound exceeds 1.5 mol, the unreacted cross-linking amino compound acts as a thermoplastic agent, and there is a tendency to reduce the heat resistance of the adhesive layer.

[0153] The crosslinking is formed by allowing the ketone group in the adhesive polyimide to react with the functional group of the crosslinking agent through a nucleophilic addition reaction, thereby forming a crosslinked polyimide as a cured product. The conditions for the nucleophilic addition reaction for crosslinking are not particularly limited and can be selected according to the type of crosslinking agent. For example, when the primary amino group of the crosslinking amino compound reacts with the ketone group in the adhesive polyimide, an imide bond (C=N bond) is generated by a condensation reaction caused by heating, thereby forming a crosslinked structure. The conditions for the condensation reaction for crosslinking are not particularly limited as long as the ketone group in the adhesive polyimide forms an imide bond (C=N bond) with the primary amino group of the crosslinking amino compound. Regarding the temperature of the heating condensation, for example, it is preferably in the range of 120°C to 220°C, and more preferably in the range of 140°C to 200°C, in order to release the water generated by the condensation to the outside of the system, or to simplify the condensation process when the heating condensation reaction is carried out after the synthesis of the adhesive polyimide. The reaction time is preferably about 30 minutes to 24 hours. The end point of the reaction can be measured by, for example, using a Fourier transform infrared spectrophotometer (commercially available product: FT / IR620 manufactured by JASCO Corporation) to measure the infrared absorption spectrum and using 1670cm -1 The decrease or disappearance of the absorption peak derived from the ketone group in the polyimide resin near 1635 cm -1 This can be confirmed by the appearance of an absorption peak derived from an imine group in the vicinity.

[0154] The heat condensation of the ketone group of the adhesive polyimide and the primary amino group of the crosslinking amino compound can be performed, for example, by the following method.

[0155] (1) A method in which an amino compound for crosslinking is added immediately after the synthesis (imidization) of the adhesive polyimide and then heated;

[0156] (2) A method in which an excess amount of an amino compound is added as a diamine component in advance, and then the adhesive polyimide is synthesized (imidized), and the remaining amino compound that does not participate in imidization or amidation is used as an amino compound for crosslinking and heated together with the adhesive polyimide;

[0157] or

[0158] (3) A method in which the adhesive polyimide composition to which the crosslink-forming amino compound is added is processed into a predetermined shape (for example, applied onto an arbitrary substrate or formed into a film) and then heated.

[0159] In order to impart heat resistance to adhesive polyimide, an example of a cross-linked polyimide that forms a cross-linked structure by forming an imide bond is given for explanation, but the present invention is not limited to this. As a method for curing the polyimide, for example, epoxy resin, epoxy resin hardener, maleimide, activated ester resin, resin having a styrene skeleton, and other compounds having unsaturated bonds can also be formulated for curing.

[0160] The first adhesive layer B1 and the second adhesive layer B2 constituting the resin film A may each contain, as appropriate, plasticizers, other resin components such as epoxy resins, hardeners, hardening accelerators, organic fillers, inorganic fillers, coupling agents, flame retardants, and the like as optional components.

[0161] When resin film A is applied to a circuit substrate, for example, in order to suppress the deterioration of dielectric loss, the dielectric loss tangent (Tanδ) at 10 GHz is preferably 0.005 or less, more preferably 0.0035 or less, and further preferably 0.0025 or less. If the dielectric loss tangent at 10 GHz of resin film A exceeds 0.005, when applied to a circuit substrate, it is easy to cause undesirable conditions such as loss of electrical signals on the transmission path of high-frequency signals. On the other hand, the lower limit of the dielectric loss tangent at 10 GHz of resin film A is not particularly limited.

[0162] When the resin film A is applied to a circuit substrate, for example, in order to ensure impedance matching, the relative dielectric constant at 10 GHz is preferably 4.0 or less, more preferably 3.5 or less, and further preferably 3.0 or less. If the relative dielectric constant of the resin film A at 10 GHz exceeds 4.0, when applied to a circuit substrate, the dielectric loss of the resin film A deteriorates, and it is easy to cause undesirable conditions such as loss of electrical signals in the transmission path of high-frequency signals.

[0163] The resin film A preferably has the following relationship when the thickness of the liquid crystal polymer layer L is TL, the thickness of the first adhesive layer B1 is TB1, and the thickness of the second adhesive layer B2 is TB2.

[0164] 0.15≦(TB1+TB2) / (TL+TB1+TB2)≦0.70

[0165] If the ratio of the total thickness of the first adhesive layer B1 and the second adhesive layer B2 to the total thickness of the resin film A is less than 0.15, the dimensional change rate after heating becomes larger and the dimensional stability may be damaged. If it is greater than 0.70, it is difficult to obtain the improvement effect of the overall dielectric properties of the resin film A brought by the liquid crystal polymer.

[0166] Here, the thickness TL of the liquid crystal polymer layer L is not particularly limited, and is preferably within a range of 25 μm to 250 μm, and more preferably within a range of 50 μm to 100 μm. In addition, the thickness TB1 of the first adhesive layer B1 and the thickness TB2 of the second adhesive layer B2 are not particularly limited, and are preferably within a range of 1 μm to 100 μm, and more preferably within a range of 5 μm to 50 μm, respectively.

[0167] The resin film A may be a film (sheet) comprising a liquid crystal polymer layer L, a first adhesive layer B1 and a second adhesive layer B2, and may be, for example, a layer stacked on a substrate of an inorganic material such as copper foil or a glass plate, or a resin substrate such as a polyimide film, a polyamide film or a polyester film.

[0168] The method for producing the resin film A of the present embodiment is not particularly limited. When the first adhesive layer B1 and the second adhesive layer B2 are polyimide layers obtained from an adhesive polyimide, the following methods [1] to [3] may be used.

[0169] [1] A method in which an adhesive polyimide is applied in a solution state (e.g., in a polyimide composition state) on one side of a liquid crystal polymer film to form a coating film, the coating film is dried at a temperature of, for example, 80°C to 180°C, and then, a coating film obtained from the adhesive polyimide is similarly formed on the other side, and the coating film is heated and dried to form a resin film A.

[0170] [2] A method of coating a solution of a polyamic acid, which is a precursor of an adhesive polyimide, on an arbitrary substrate and drying it, then imidizing it and forming it into a film, and then peeling it from the substrate. A liquid crystal polymer film is sandwiched between two polyimide films obtained in the above manner, and they are thermally pressed to form a resin film A.

[0171] [3] A method in which a solution of a polyamic acid, which is a precursor of an adhesive polyimide, is applied to an arbitrary substrate and dried, and then a gel film of the polyamic acid is peeled off from the substrate. A liquid crystal polymer film is sandwiched between two gel films obtained in the above manner and the two films are thermally pressed to form a resin film A while imidizing.

[0172] The method for applying the adhesive polyimide solution (or polyamic acid solution) onto the substrate is not particularly limited, and the substrate can be applied using, for example, a coater such as a notch wheel, a die, a knife, or a die lip.

[0173] The resin film A obtained in the above manner has a sandwich structure in which a liquid crystal polymer layer L is sandwiched by a first adhesive layer B1 and a second adhesive layer B2 having a predetermined storage elastic modulus, and thus has excellent dielectric properties and dimensional stability. Therefore, the resin film A can be preferably used as, for example, an adhesive film (joining sheet) or an adhesive layer constituting a part of an insulating resin layer of a circuit substrate. By applying the resin film A, the transmission loss during high-frequency signal transmission can be reduced in the circuit substrate, and dimensional stability can be ensured.

[0174] [Metal-clad laminate]

[0175] Figure 2 Schematic diagram showing the structure of a metal-clad laminate according to one embodiment of the present invention. The metal-clad laminate (C) according to this embodiment has a structure in which a pair of single-sided metal-clad laminates are bonded together via an adhesive layer (A').

[0176] That is, the metal-clad laminate (C) includes a first single-sided metal-clad laminate (C1), a second single-sided metal-clad laminate (C2), and an adhesive layer (A') laminated between the first single-sided metal-clad laminate (C1) and the second single-sided metal-clad laminate (C2). Here, the adhesive layer (A') includes the resin film A.

[0177] In addition, the first single-sided metal-clad laminate (C1) has a first metal layer (M1) and a first insulating resin layer (P1) laminated on at least one side of the first metal layer (M1). The second single-sided metal-clad laminate (C2) has a second metal layer (M2) and a second insulating resin layer (P2) laminated on at least one side of the second metal layer (M2). The adhesive layer (A') is arranged in contact with the first insulating resin layer (P1) and the second insulating resin layer (P2). That is, the metal-clad laminate (C) has a structure in which the first metal layer (M1) / first insulating resin layer (P1) / adhesive layer (A') / second insulating resin layer (P2) / second metal layer (M2) are laminated in this order. The first metal layer (M1) and the second metal layer (M2) are located at the outermost sides respectively, and the first insulating resin layer (P1) and the second insulating resin layer (P2) are arranged inside them, and an adhesive layer (A') is arranged between the first insulating resin layer (P1) and the second insulating resin layer (P2).

[0178] The structure of the pair of single-sided metal-clad laminates (C1, C2) is not particularly limited, and common materials can be used as FPC materials, and commercially available copper-clad laminates, etc. Furthermore, the structures of the first single-sided metal-clad laminate (C1) and the second single-sided metal-clad laminate (C2) may be the same or different.

[0179] (Metal layer)

[0180] The material of the first metal layer (M1) and the second metal layer (M2) is not particularly limited, and examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among them, copper or copper alloys are particularly preferred. Furthermore, the material of the wiring layer in the circuit substrate of the present embodiment described later is also the same as the first metal layer (M1) and the second metal layer (M2).

[0181] The thickness of the first metal layer (M1) and the second metal layer (M2) is not particularly limited. For example, when using a metal foil such as copper foil, it is preferably 35 μm or less, and more preferably within the range of 5 μm to 25 μm. From the perspective of production stability and handling properties, the lower limit of the thickness of the metal foil is preferably set to 5 μm. Furthermore, when using copper foil, it can be a rolled copper foil or an electrolytic copper foil. In addition, as the copper foil, a commercially available copper foil can be used.

[0182] The metal foil may be subjected to surface treatment using, for example, siding, aluminum alcoholate, aluminum chelate, silane coupling agent, etc., for the purpose of rust prevention or improvement of adhesive strength.

[0183] (Insulating resin layer)

[0184] The first insulating resin layer (P1) and the second insulating resin layer (P2) are not particularly limited if they contain a resin having electrical insulation properties, and examples thereof include polyimide, epoxy resin, phenolic resin, polyethylene, polypropylene, polytetrafluoroethylene, silicone, ethylene tetrafluoroethylene (ETFE), etc., preferably polyimide. In addition, the first insulating resin layer (P1) and the second insulating resin layer (P2) are not limited to a single layer, and multiple resin layers may be stacked. Furthermore, when referred to as polyimide in the present invention, in addition to polyimide, it also refers to a resin containing a polymer having an imide group in the molecular structure, such as polyamide-imide, polyether-imide, polyester-imide, polysiloxane-imide, and polybenzimidazole-imide.

[0185] <Layer thickness>

[0186] When the total thickness of the first insulating resin layer (P1), the adhesive layer (A') and the second insulating resin layer (P2) of the metal-clad laminate (C) is T1, the total thickness T1 is in the range of 50 μm to 500 μm, preferably in the range of 100 μm to 300 μm. If the total thickness T1 is less than 50 μm, the effect of reducing the transmission loss when the circuit substrate is made is insufficient, and if it exceeds 500 μm, there is a risk that the bendability of the circuit substrate is reduced or the productivity is reduced.

[0187] In addition, the thickness T2 of the adhesive layer (A') (i.e., TL+TB1+TB2 in the resin film A) is preferably in the range of 26 μm to 350 μm, and more preferably in the range of 30 μm to 250 μm. If the thickness T2 of the adhesive layer (A') is less than the lower limit, there is a case where the transmission loss becomes large as a high-frequency substrate. On the other hand, if the thickness of the adhesive layer (A') exceeds the upper limit, there is a case where undesirable conditions such as reduced dimensional stability occur.

[0188] In addition, the ratio (T2 / T1) of the thickness T2 of the adhesive layer (A') to the total thickness T1 is in the range of 0.50 to 0.90, preferably in the range of 0.5 to 0.8. If the ratio (T2 / T1) is less than 0.5, it is difficult to set T1 to 50 μm or more, and the effect of reducing the transmission loss when the circuit substrate is made is insufficient. If it exceeds 0.90, undesirable conditions such as reduced dimensional stability occur.

[0189] The thickness T3 of the first insulating resin layer (P1) and the second insulating resin layer (P2) is preferably within the range of 12 μm to 100 μm, and more preferably within the range of 12 μm to 50 μm. If the thickness T3 of the first insulating resin layer (P1) and the second insulating resin layer (P2) is less than the lower limit value, there is a situation where problems such as warping of the metal-clad laminate (C) occur. If the thickness T3 of the first insulating resin layer (P1) and the second insulating resin layer (P2) exceeds the upper limit value, undesirable conditions such as reduced productivity occur. Furthermore, the first insulating resin layer (P1) and the second insulating resin layer (P2) do not necessarily have to be the same thickness.

[0190] <Coefficient of thermal expansion>

[0191] The first insulating resin layer (P1) and the second insulating resin layer (P2) preferably have a thermal expansion coefficient (CTE) of 10 ppm / K or more, preferably within a range of 10 ppm / K or more and 30 ppm / K or less, and more preferably within a range of 15 ppm / K or more and 25 ppm / K or less. If the CTE is less than 10 ppm / K or exceeds 30 ppm / K, warping or reduced dimensional stability may occur. By appropriately changing the combination of raw materials used, thickness, and drying / hardening conditions, a polyimide layer having a desired CTE may be produced.

[0192] The first adhesive layer B1 and the second adhesive layer B2 have low elasticity and low glass transition temperature, so even if the CTE of the adhesive layer (A') as a whole exceeds 30ppm / K, the internal stress generated during lamination can be alleviated. In addition, the thermal expansion coefficient (CTE) of the first insulating resin layer (P1), the adhesive layer (A') and the second insulating resin layer (P2) as a whole is preferably 10ppm / K or more, preferably in the range of 10ppm / K or more and 30ppm / K or less, and more preferably in the range of 15ppm / K or more and 25ppm / K or less. If the CTE of these resin layers as a whole is less than 10ppm / K or exceeds 30ppm / K, warping will occur or dimensional stability will be reduced.

[0193] <Dielectric loss tangent>

[0194] For example, when the first insulating resin layer (P1) and the second insulating resin layer (P2) are applied to a circuit substrate, in order to suppress the deterioration of dielectric loss, the dielectric loss tangent (Tanδ) at 10 GHz is preferably less than 0.02, more preferably less than 0.01, and further preferably less than 0.008. If the dielectric loss tangent at 10 GHz of the first insulating resin layer (P1) and the second insulating resin layer (P2) exceeds 0.02, when applied to a circuit substrate, it is easy to cause undesirable conditions such as loss of electrical signals on the transmission path of high-frequency signals. On the other hand, there is no particular restriction on the lower limit of the dielectric loss tangent at 10 GHz of the first insulating resin layer (P1) and the second insulating resin layer (P2), but the physical property control of the insulating resin layer as a circuit substrate should be considered.

[0195] <Relative dielectric constant>

[0196] When the first insulating resin layer (P1) and the second insulating resin layer (P2) are used as insulating resin layers of a circuit substrate, for example, the relative dielectric constant of the insulating resin layer as a whole at 10 GHz is preferably 4.0 or less in order to ensure impedance matching. If the relative dielectric constant of the first insulating resin layer (P1) and the second insulating resin layer (P2) at 10 GHz exceeds 4.0, when applied to a circuit substrate, the dielectric loss of the first insulating resin layer (P1) and the second insulating resin layer (P2) deteriorates, and it is easy to cause disadvantages such as loss of electrical signals in the transmission path of high-frequency signals.

[0197] <Function>

[0198] In the metal-clad laminate (C), a liquid crystal polymer layer L is provided in the adhesive layer (A') in order to achieve a low dielectric loss tangent of the entire insulating resin layer and to cope with high-frequency signal transmission. However, the liquid crystal polymer layer L has a large dimensional change rate before and after heating, so there is a risk that the dimensional stability will be reduced as the thickness of the liquid crystal polymer layer L is increased.

[0199] Therefore, in the metal-clad laminate (C) of the present embodiment, as the adhesive layer (A'), a sandwich structure is set in which the liquid crystal polymer layer L is sandwiched by the first adhesive layer B1 and the second adhesive layer B2 having a low storage elastic modulus, thereby alleviating the internal stress generated by heating to ensure dimensional stability. In particular, when a polyimide containing 50 mol % or more of a diamine residue derived from a diamine derived from a dimer acid in which both terminal carboxylic acid groups of a dimer acid are substituted with a primary aminomethyl group or an amino group is used as the material of the first adhesive layer B1 and the second adhesive layer B2, the dimensional stability can be improved without increasing the relative dielectric constant and dielectric loss tangent of the adhesive layer (A') as a whole.

[0200] In addition, the adhesive layer (A') is stacked between the first insulating resin layer (P1) and the second insulating resin layer (P2), thereby functioning as an intermediate layer to suppress warping and dimensional changes. Furthermore, even in a heating process such as reflow soldering when mounting a semiconductor chip, direct contact with heat or oxygen can be blocked by the first insulating resin layer (P1) or the second insulating resin layer (P2), so that the adhesive layer (A') is not easily affected by oxidative degradation and is not easily dimensionally changed. As described above, there are also advantages brought about by the characteristics of the layer structure of the first insulating resin layer (P1), the adhesive layer (A') and the second insulating resin layer (P2).

[0201] [Manufacturing of Metal-Clad Laminated Plate]

[0202] The metal-clad laminate (C) can be manufactured, for example, by the following method: a resin film A serving as an adhesive layer (A') is arranged between a first insulating resin layer (P1) of a first single-sided metal-clad laminate (C1) and a second insulating resin layer (P2) of a second single-sided metal-clad laminate (C2), and the two are bonded together and then thermocompression-bonded.

[0203] The metal-clad laminate (C) of the present embodiment obtained in the above manner can be manufactured into a circuit board such as a single-sided FPC or a double-sided FPC by etching the first metal layer (M1) and / or the second metal layer (M2) and performing wiring circuit processing.

[0204] [Preferred structural example of metal-clad laminate]

[0205] Next, the first insulating resin layer (P1), the second insulating resin layer (P2), the adhesive layer (A'), the first metal layer (M1), and the second metal layer (M2) in the metal-clad laminate (C) of the present embodiment will be described in more detail.

[0206] Figure 3 Schematic cross-sectional view showing the structure of the metal-clad laminate 100 according to this embodiment. Figure 3As shown, the metal-clad laminate 100 includes metal layers 101, 101 as the first metal layer (M1) and the second metal layer (M2), polyimide layers 110, 110 as the first insulating resin layer (P1) and the second insulating resin layer (P2), and an adhesive layer 120 as an adhesive layer (A'). Here, a single-sided metal-clad laminate 130 as a first single-sided metal-clad laminate (C1) or a second single-sided metal-clad laminate (C2) is formed by the metal layer 101 and the polyimide layer 110. In this embodiment, the first single-sided metal-clad laminate (C1) and the second single-sided metal-clad laminate (C2) have the same structure.

[0207] The polyimide layers 110 and 110 may be a structure formed by stacking a plurality of polyimide layers. Figure 3 In the illustrated embodiment, a three-layer structure is formed including non-thermoplastic polyimide layers 111, 111 including non-thermoplastic polyimide as a base layer and thermoplastic polyimide layers 112, 112 including thermoplastic polyimide provided on both sides of the non-thermoplastic polyimide layers 111, 111. In addition, the polyimide layers 110, 110 are not limited to a three-layer structure.

[0208] exist Figure 3 In the metal-clad laminate 100 shown, the outer thermoplastic polyimide layers 112, 112 of the two single-sided metal-clad laminates 130, 130 are respectively bonded to the adhesive layer 120, thereby forming the metal-clad laminate 100. The adhesive layer 120 is an adhesive layer for bonding the two single-sided metal-clad laminates 130, 130 in the metal-clad laminate 100, and is used to ensure dimensional stability and thicken the insulating resin layer of the metal-clad laminate 100. The adhesive layer 120 is as described for the adhesive layer (A').

[0209] Next, the non-thermoplastic polyimide layer 111 and the thermoplastic polyimide layer 112 constituting the polyimide layers 110 and 110 are described. The so-called "non-thermoplastic polyimide" is generally a polyimide that does not show softening and adhesiveness even when heated, but in the present invention, it refers to a polyimide having a storage elastic modulus of 1.0×10 9 Pa or more and the storage elastic modulus at 350°C is 1.0×10 8 The so-called "thermoplastic polyimide" is generally a polyimide whose glass transition temperature (Tg) can be clearly confirmed, but in the present invention, it means a polyimide whose storage elastic modulus at 30°C measured by DMA is 1.0×10 9Pa or more and the storage elastic modulus at 350°C is less than 1.0×10 8 Polyimide of Pa.

[0210] Non-thermoplastic polyimide layer:

[0211] The non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer 111 contains a tetracarboxylic acid residue and a diamine residue. The non-thermoplastic polyimide preferably contains an aromatic tetracarboxylic acid residue derived from an aromatic tetracarboxylic dianhydride and an aromatic diamine residue derived from an aromatic diamine.

[0212] (Tetracarboxylic acid residue)

[0213] The non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer 111 preferably contains a tetracarboxylic acid residue derived from at least one of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and 1,4-phenylene bis(trimellitic acid monoester) dianhydride (TAHQ) and a tetracarboxylic acid residue derived from at least one of pyromellitic dianhydride (PMDA) and 2,3,6,7-naphthalene tetracarboxylic dianhydride (NTCDA) as the tetracarboxylic acid residue.

[0214] The tetracarboxylic acid residue derived from BPDA (hereinafter, also referred to as "BPDA residue") and the tetracarboxylic acid residue derived from TAHQ (hereinafter, also referred to as "TAHQ residue") easily form an ordered structure of the polymer, and can reduce the dielectric loss tangent or hygroscopicity by inhibiting the movement of molecules. The BPDA residue can impart self-supporting properties to the gel film of polyamic acid, which is a polyimide precursor, but on the other hand, there is a tendency to increase the CTE after imidization, reduce the glass transition temperature, and reduce the heat resistance.

[0215] According to this viewpoint, the non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer 111 is controlled to contain BPDA residues and TAHQ residues in a total range of preferably 30 mol parts or more and 60 mol parts or less, and more preferably 40 mol parts or more and 50 mol parts or less relative to 100 mol parts of all tetracarboxylic acid residues. If the total amount of BPDA residues and TAHQ residues is less than 30 mol parts, the formation of the ordered structure of the polymer becomes insufficient, the hygroscopicity resistance is reduced, or the reduction of the dielectric loss tangent becomes insufficient. If it exceeds 60 mol parts, in addition to the increase in CTE or the increase in the amount of change in the in-plane delay (RO), there is also the risk of reduced heat resistance.

[0216] In addition, tetracarboxylic acid residues derived from pyromellitic acid dianhydride (hereinafter, also referred to as "PMDA residues") and tetracarboxylic acid residues derived from 2,3,6,7-naphthalenetetracarboxylic acid dianhydride (hereinafter, also referred to as "NTCDA residues") are rigid, and therefore improve in-plane orientation, suppress CTE to a low level, and assume the role of controlling in-plane delay (RO) or controlling glass transition temperature. On the other hand, PMDA residues are due to their small molecular weight, so if their amount becomes too much, the imide concentration of the polymer becomes high, the polar group increases and the hygroscopicity becomes large, and the dielectric loss tangent increases due to the influence of moisture inside the molecular chain. In addition, NTCDA residues have a tendency to make the film easily brittle and increase the elastic modulus due to the high naphthalene skeleton of rigidity.

[0217] Therefore, the non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer contains PMDA residues and NTCDA residues in a total of preferably 40 mol parts or more and 70 mol parts or less, more preferably 50 mol parts or more and 60 mol parts or less, and more preferably 50 mol parts to 55 mol parts relative to 100 mol parts of all tetracarboxylic acid residues. If the total of PMDA residues and NTCDA residues is less than 40 mol parts, there is a risk of CTE increase or heat resistance reduction, and if it exceeds 70 mol parts, there is a risk of the imide group concentration of the polymer becoming high, the polar group increases and the low hygroscopicity is impaired, and the dielectric loss tangent increases; or the film becomes brittle and the self-supporting property of the film is reduced.

[0218] The total amount of at least one of BPDA residue and TAHQ residue and at least one of PMDA residue and NTCDA residue is preferably 80 mol parts or more, preferably 90 mol parts or more, based on 100 mol parts of all tetracarboxylic acid residues.

[0219] In addition, it is preferable to control the CTE and the formation of an ordered structure of the polymer by setting the molar ratio of at least one of BPDA residues and TAHQ residues to at least one of PMDA residues and NTCDA residues {(BPDA residue + TAHQ residue) / (PMDA residue + NTCDA residue)} to a range of greater than 0.4 and less than 1.5, preferably within a range of greater than 0.6 and less than 1.3, and more preferably within a range of greater than 0.8 and less than 1.2.

[0220] PMDA and NTCDA have a rigid skeleton, so compared with other common anhydride components, the in-plane orientation of the molecules in the polyimide can be controlled, and the thermal expansion coefficient (CTE) is suppressed and the glass transition temperature (Tg) is improved. In addition, compared with PMDA, the molecular weight of BPDA and TAHQ is larger, so the imide group concentration is reduced due to the increase in the input ratio, which has an effect on the reduction of the dielectric loss tangent or the reduction of the hygroscopicity. On the other hand, if the input ratio of BPDA and TAHQ increases, the in-plane orientation of the molecules in the polyimide is reduced, which leads to an increase in CTE. And then, the formation of the ordered structure in the molecule is promoted, and the haze value increases. From this point of view, the total input amount of PMDA and NTCDA is in the range of 40 to 70 molar parts relative to 100 molar parts of all anhydride components of the raw material, preferably in the range of 50 to 60 molar parts, and more preferably in the range of 50 to 55 molar parts. If the total amount of PMDA and NTCDA is less than 40 parts by mole relative to 100 parts by mole of all the anhydride components of the raw material, the in-plane orientation of the molecules is reduced, and it becomes difficult to lower the CTE. In addition, the heat resistance or dimensional stability of the film during heating caused by the reduction in Tg is reduced. On the other hand, if the total amount of PMDA and NTCDA exceeds 70 parts by mole, there is a tendency to deteriorate the moisture absorption rate or increase the elastic modulus due to the increase in the imide group concentration.

[0221] In addition, BPDA and TAHQ have an effect on lowering the dielectric loss tangent and reducing the moisture absorption rate caused by the suppression of molecular motion or the reduction of the imide group concentration, but increase the CTE of the polyimide film after imidization. From this point of view, the total input amount of BPDA and TAHQ is preferably within the range of 30 to 60 mol parts, preferably within the range of 40 to 50 mol parts, and more preferably within the range of 40 to 45 mol parts relative to 100 mol parts of all the anhydride components of the raw materials.

[0222] Examples of tetracarboxylic acid residues other than the BPDA residue, TAHQ residue, PMDA residue, and NTCDA residue contained in the non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer 111 include 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-benzophenone tetracarboxylic dianhydride, 2,3,3',4'-benzophenone tetracarboxylic dianhydride or 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 2,3',3,4'-diphenyl ether tetracarboxylic dianhydride, and bis(2,3-dicarboxyphenyl)ether dianhydride. , 3,3",4,4"-terphenyltetracarboxylic dianhydride, 2,3,3",4"-terphenyltetracarboxylic dianhydride or 2,2",3,3"-terphenyltetracarboxylic dianhydride, 2,2-bis(2,3-dicarboxyphenyl)-propane dianhydride or 2,2-bis(3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride or bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)sulfone dianhydride or bis(3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride or 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,2,7,8-phenanthrene -tetracarboxylic dianhydride, 1,2,6,7-phenanthrene-tetracarboxylic dianhydride or 1,2,9,10-phenanthrene-tetracarboxylic dianhydride, 2,3,6,7-anthracenetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)tetrafluoropropane dianhydride, 2,3,5,6-cyclohexane dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic dianhydride, 2,6-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-(or 1,4,5,8- ) tetracarboxylic acid residues derived from aromatic tetracarboxylic acid dianhydrides such as tetrachloronaphthalene-1,4,5,8-(or 2,3,6,7-)tetracarboxylic dianhydride, 2,3,8,9-perylene-tetracarboxylic dianhydride, 3,4,9,10-perylene-tetracarboxylic dianhydride, 4,5,10,11-perylene-tetracarboxylic dianhydride or 5,6,11,12-perylene-tetracarboxylic dianhydride, cyclopentane-1,2,3,4-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, 4,4'-bis(2,3-dicarboxyphenoxy)diphenylmethane dianhydride, and ethylene glycol ditrimellitate dianhydride.

[0223] (Diamine residue)

[0224] As the diamine residue contained in the non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer 111 , a diamine residue derived from a diamine compound represented by the general formula (A1) is preferred.

[0225] [Chemistry 6]

[0226]

[0227] In formula (A1), the linking group Z represents a single bond or -COO-, Y independently represents a monovalent hydrocarbon group with 1 to 3 carbon atoms which may be substituted with a halogen atom or a phenyl group, or an alkoxy group with 1 to 3 carbon atoms or a perfluoroalkyl or alkenyl group with 1 to 3 carbon atoms, n represents an integer of 0 to 2, and p and q independently represent integers of 0 to 4. Here, the term "independently" means that in the formula (A1), a plurality of substituents Y, and integers p and q may be the same or different. Furthermore, in the formula (A1), the hydrogen atoms in the two amino groups at the terminals may be substituted, for example, -NR2R3 (here, R2 and R3 independently refer to any substituent such as an alkyl group).

[0228] The diamine compound represented by the general formula (A1) (hereinafter, sometimes referred to as "diamine (A1)") is an aromatic diamine having one or three benzene rings. Since diamine (A1) has a rigid structure, it has the effect of imparting an ordered structure to the polymer as a whole. Therefore, a polyimide with low air permeability and low hygroscopicity can be obtained, which can reduce the moisture inside the molecular chain, thereby reducing the dielectric loss tangent. Here, as a linking group Z, a single bond is preferred.

[0229] Examples of the diamine (A1) include 1,4-diaminobenzene (p-PDA (p-phenylenediamine); p-phenylenediamine), 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 2,2'-n-propyl-4,4'-diaminobiphenyl (m-NPB), and 4-aminophenyl-4'-aminobenzoate (APAB).

[0230] The non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer 111 preferably contains 80 mol parts or more, more preferably 85 mol parts or more of diamine residues derived from the diamine (A1) relative to 100 mol parts of all diamine residues. By using the diamine (A1) in an amount within the above range, it is easy to form an ordered structure in the entire polymer by utilizing the rigid structure derived from the monomer, and it is easy to obtain a non-thermoplastic polyimide with low air permeability, low hygroscopicity and low dielectric loss tangent.

[0231] When the amount of the diamine residue derived from the diamine (A1) is in the range of 80 parts by mole or more and 85 parts by mole or less based on 100 parts by mole of all the diamine residues in the non-thermoplastic polyimide, 1,4-diaminobenzene is preferably used as the diamine (A1) from the viewpoint of having a more rigid structure and excellent in-plane orientation.

[0232] Examples of other diamine residues contained in the non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer 111 include 2,2-bis-[4-(3-aminophenoxy)phenyl]propane, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)]biphenyl, bis[1-(3-aminophenoxy)]biphenyl, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)]benzophenone, 9,9-bis[4-(3-aminophenoxy)phenyl]fluorene, 2,2-bis-[4-(4 -aminophenoxy)phenyl]hexafluoropropane, 2,2-bis-[4-(3-aminophenoxy)phenyl]hexafluoropropane, 3,3'-dimethyl-4,4'-diaminobiphenyl, 4,4'-methylenebis-o-toluidine, 4,4'-methylenebis-2,6-dimethylaniline, 4,4'-methylenebis-2,6-diethylaniline, 3,3'-diaminodiphenylethane, 3,3'-diaminobiphenyl, 3,3'-dimethoxybenzidine, 3,3"-diamino-p-terphenyl, 4,4'-[1,4-phenylenebis(1-methylethylidene)]dianiline, 4,4'-[1,3-phenylenebis (1-methylethylidene)] dianiline, bis(p-aminocyclohexyl)methane, bis(p-β-amino-tert-butylphenyl) ether, bis(p-β-methyl-δ-aminopentyl)benzene, p-bis(2-methyl-4-aminopentyl)benzene, p-bis(1,1-dimethyl-5-aminopentyl)benzene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,4-bis(β-amino-tert-butyl)toluene, 2,4-diaminotoluene, m-xylene-2,5-diamine, p-xylene-2,5-diamine, m-xylylenediamine, p-xylylenediamine diamine residues derived from aromatic diamine compounds such as 2,6-diaminopyridine, 2,5-diaminopyridine, 2,5-diamino-1,3,4-oxadiazole, piperazine, 2'-methoxy-4,4'-diaminobenzanilide, 4,4'-diaminobenzanilide, 1,3-bis[2-(4-aminophenyl)-2-propyl]benzene, and 6-amino-2-(4-aminophenoxy)benzoxazole; and diamine residues derived from aliphatic diamine compounds such as diamine derived from dimer acid in which both terminal carboxylic acid groups of a dimer acid are substituted with a primary aminomethyl group or an amino group.

[0233] By selecting the types of the tetracarboxylic acid residue and the diamine residue in the non-thermoplastic polyimide, or the respective molar ratios when two or more tetracarboxylic acid residues or diamine residues are used, the thermal expansion coefficient, storage elastic modulus, tensile elastic modulus, etc. can be controlled. In addition, when there are a plurality of polyimide structural units in the non-thermoplastic polyimide, they may exist in the form of blocks or randomly, but from the viewpoint of suppressing the deviation of the in-plane retardation (RO), they are preferably randomly present.

[0234] Furthermore, by making both the tetracarboxylic acid residue and the diamine residue contained in the non-thermoplastic polyimide an aromatic group, the dimensional accuracy of the polyimide film in a high temperature environment can be improved and the variation amount of the in-plane retardation (RO) can be reduced, which is preferred.

[0235] The imide group concentration of the non-thermoplastic polyimide is preferably 33% or less, more preferably 32% or less. Here, "imide group concentration" refers to the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the entire structure of the polyimide. If the imide group concentration exceeds 33%, the molecular weight of the resin itself becomes smaller, and the low hygroscopicity is also deteriorated due to the increase in polar groups. By selecting the combination of the acid anhydride and the diamine compound to control the orientation of the molecules in the non-thermoplastic polyimide, the increase in CTE associated with the decrease in the imide group concentration is suppressed, thereby ensuring low hygroscopicity.

[0236] The weight average molecular weight of the non-thermoplastic polyimide is preferably in the range of 10,000 to 400,000, and more preferably in the range of 50,000 to 350,000. If the weight average molecular weight is less than 10,000, the strength of the film is reduced and the film tends to be brittle. On the other hand, if the weight average molecular weight exceeds 400,000, the viscosity is excessively increased, and defects such as uneven film thickness and streaks are easily generated during coating.

[0237] From the viewpoint of ensuring the function as a base layer and the transportability during manufacturing and thermoplastic polyimide coating, the thickness of the non-thermoplastic polyimide layer 111 is preferably within the range of 6 μm to 100 μm, and more preferably within the range of 9 μm to 50 μm. When the thickness of the non-thermoplastic polyimide layer 111 is less than the lower limit, the electrical insulation or handling property becomes insufficient, and when the thickness exceeds the upper limit, the productivity decreases.

[0238] From the viewpoint of heat resistance, the glass transition temperature (Tg) of the non-thermoplastic polyimide layer 111 is preferably 280° C. or higher.

[0239] In addition, from the perspective of suppressing warping, the thermal expansion coefficient of the non-thermoplastic polyimide layer 111 is preferably in the range of 1 ppm / K to 30 ppm / K, preferably in the range of 1 ppm / K to 25 ppm / K, and more preferably in the range of 10 ppm / K to 20 ppm / K.

[0240] In addition, other curing resin components such as plasticizers, epoxy resins, curing agents, curing accelerators, coupling agents, fillers, solvents, flame retardants, etc. may be appropriately formulated as arbitrary components in the non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer 111. However, some plasticizers contain a large number of polar groups, and there is a concern that they promote the diffusion of copper from copper wiring, so it is preferably not to use plasticizers as much as possible.

[0241] Thermoplastic polyimide layer:

[0242] The thermoplastic polyimide constituting the thermoplastic polyimide layer 112 contains a tetracarboxylic acid residue and a diamine residue, and preferably contains an aromatic tetracarboxylic acid residue derived from an aromatic tetracarboxylic dianhydride and an aromatic diamine residue derived from an aromatic diamine.

[0243] (Tetracarboxylic acid residue)

[0244] As the tetracarboxylic acid residue used in the thermoplastic polyimide constituting the thermoplastic polyimide layer 112 , the same groups as exemplified as the tetracarboxylic acid residue in the non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer 111 can be used.

[0245] (Diamine residue)

[0246] As the diamine residue contained in the thermoplastic polyimide constituting the thermoplastic polyimide layer 112 , a diamine residue derived from the diamine compound represented by the general formula (B1) to the general formula (B7) described above for the adhesive polyimide is preferred.

[0247] The thermoplastic polyimide constituting the thermoplastic polyimide layer 112 preferably contains diamine residues derived from at least one diamine compound selected from diamine (B1) to diamine (B7) in an amount of 60 mol parts or more, preferably in a range of 60 mol parts or more and 99 mol parts or less, and more preferably in a range of 70 mol parts or more and 95 mol parts or less, relative to 100 mol parts of all diamine residues. Diamine (B1) to diamine (B7) contain a molecular structure having flexibility, so by using at least one diamine compound selected from these in an amount within the above range, the flexibility of the polyimide molecular chain can be improved and thermoplasticity can be imparted. If the total amount of diamine (B1) to diamine (B7) in the raw material is less than 60 mol parts relative to 100 mol parts of all diamine components, sufficient thermoplasticity cannot be obtained due to insufficient flexibility of the polyimide resin.

[0248] In addition, as the diamine residue contained in the thermoplastic polyimide constituting the thermoplastic polyimide layer 112, it is also preferably a diamine residue derived from a diamine compound represented by the general formula (A1). About the diamine compound [diamine (A1)] represented by the formula (A1), as described in the description of the non-thermoplastic polyimide. Diamine (A1) has a rigid structure and has the effect of imparting an ordered structure to the polymer as a whole, so that the dielectric loss tangent or hygroscopicity can be reduced by suppressing the movement of molecules. And then, by being used as the raw material of the thermoplastic polyimide, a polyimide with low air permeability and excellent long-term heat-resistant adhesion can be obtained.

[0249] The thermoplastic polyimide constituting the thermoplastic polyimide layer 112 may contain a diamine residue derived from the diamine (A1) in a range of preferably 1 mol part or more and 40 mol parts or less, more preferably 5 mol parts or more and 30 mol parts or less. By using the diamine (A1) in an amount within the above range and utilizing the rigid structure derived from the monomer to form an ordered structure in the entire polymer, a thermoplastic polyimide having low air permeability and hygroscopicity and excellent long-term heat-resistant adhesiveness can be obtained.

[0250] The thermoplastic polyimide constituting the thermoplastic polyimide layer 112 may contain a diamine residue derived from a diamine compound other than the diamine (A1) and the diamines (B1) to (B7) within a range that does not impair the effects of the invention.

[0251] By selecting the types of the tetracarboxylic acid residue and the diamine residue in the thermoplastic polyimide, or the respective molar ratios when two or more tetracarboxylic acid residues or diamine residues are used, the thermal expansion coefficient, tensile elastic modulus, glass transition temperature, etc. can be controlled. In addition, when there are a plurality of polyimide structural units in the thermoplastic polyimide, they may exist in the form of blocks or randomly, but preferably randomly.

[0252] Furthermore, by making both the tetracarboxylic acid residue and the diamine residue contained in the thermoplastic polyimide an aromatic group, the dimensional accuracy of the polyimide film in a high temperature environment can be improved, and the change amount of the in-plane retardation (RO) can be suppressed.

[0253] The imide group concentration of the thermoplastic polyimide is preferably 33% or less, more preferably 32% or less. Here, "imide group concentration" refers to the value obtained by dividing the molecular weight of the imide group (-(CO)2-N-) in the polyimide by the molecular weight of the entire structure of the polyimide. If the imide group concentration exceeds 33%, the molecular weight of the resin itself becomes smaller, and the low hygroscopicity is also deteriorated due to the increase in polar groups. By selecting a combination of the diamine compounds to control the orientation of the molecules in the thermoplastic polyimide, the increase in CTE associated with the decrease in the imide group concentration is suppressed, thereby ensuring low hygroscopicity.

[0254] The weight average molecular weight of the thermoplastic polyimide is preferably in the range of 10,000 to 400,000, and more preferably in the range of 50,000 to 350,000. If the weight average molecular weight is less than 10,000, the strength of the film is reduced and the film tends to be brittle. On the other hand, if the weight average molecular weight exceeds 400,000, the viscosity is excessively increased, and defects such as uneven film thickness and streaks are easily generated during coating.

[0255] The thermoplastic polyimide constituting the thermoplastic polyimide layer 112, for example, becomes an adhesive layer in the insulating resin layer of the circuit substrate, so in order to suppress the diffusion of copper, it is most preferably a completely imidized structure. However, a portion of the polyimide may also become an amic acid. The imidization rate can be measured by using a Fourier transform infrared spectrophotometer (commercially available product: FT / IR620 manufactured by JASCO Corporation) and using the attenuated total reflection (ATR) method to measure the infrared absorption spectrum of the polyimide film at 1015 cm -1 Based on the benzene ring absorber nearby, the -1 The absorbance derived from the C=O expansion and contraction of the imide group was calculated.

[0256] From the viewpoint of ensuring the adhesive function, the thickness of the thermoplastic polyimide layer 112 is preferably within the range of 1 μm to 10 μm, and more preferably within the range of 1 μm to 5 μm. When the thickness of the thermoplastic polyimide layer 112 is less than the lower limit, the adhesiveness becomes insufficient, and when the thickness exceeds the upper limit, the dimensional stability tends to deteriorate.

[0257] From the viewpoint of suppressing warpage, the thermal expansion coefficient of the thermoplastic polyimide layer 112 is preferably 30 ppm / K or more, preferably 30 ppm / K or more and 100 ppm / K or less, and more preferably 30 ppm / K or more and 80 ppm / K or less.

[0258] In addition, in addition to polyimide, the resin used in the thermoplastic polyimide layer 112 may also be appropriately formulated with other curing resin components such as plasticizers, epoxy resins, curing agents, curing accelerators, inorganic fillers, coupling agents, fillers, solvents, flame retardants, etc. as arbitrary components. However, some plasticizers contain a large number of polar groups, and there is a concern that they promote the diffusion of copper from copper wiring, so it is preferably not to use plasticizers as much as possible.

[0259] In the metal-clad laminate 100, in order to ensure dimensional stability after circuit processing, the overall thermal expansion coefficient of the two polyimide layers 110 and the adhesive layer 120 is preferably above 10 ppm / K, preferably within the range of 10 ppm / K to 30 ppm / K, and more preferably within the range of 15 ppm / K to 25 ppm / K.

[0260] Furthermore, in the metal-clad laminate 100, the total thickness T1 of the two polyimide layers 110 and the adhesive layer 120, the thickness T2 of the adhesive layer 120, and the ratio (T2 / T1) of the thickness T2 of the adhesive layer 120 to the total thickness T1 are as follows: Figure 2 As described.

[0261] (Synthesis of Polyimide)

[0262] The polyimide constituting the polyimide layer 110 can be produced by reacting the acid anhydride and the diamine in a solvent to generate a precursor resin and then heating the resulting resin to close the ring. The polyimide can be synthesized by the method described above for the adhesive polyimide.

[0263] [Circuit board]

[0264] The metal-clad laminate 100 is mainly effectively used as a circuit substrate material such as an FPC and a rigid-flexible circuit substrate. That is, by processing one or both of the two metal layers 101 of the metal-clad laminate 100 into a pattern using a conventional method to form a wiring layer, a circuit substrate such as an FPC as an embodiment of the present invention can be manufactured. Although the circuit substrate is omitted in the figure, it includes a resin laminate formed by laminating a first insulating resin layer (P1), an adhesive layer (A'), and a second insulating resin layer (P2) in sequence, and a wiring layer provided on one side or both sides of the resin laminate.

[0265] [Example]

[0266] The following examples are shown to more specifically describe the features of the present invention. However, the scope of the present invention is not limited to the examples. Furthermore, in the following examples, unless otherwise specified, various measurements and evaluations are based on the following contents.

[0267] [Viscosity measurement]

[0268] The viscosity was measured at 25° C. using an E-type viscometer (Brookfield, trade name: DV-II+Pro). The rotation speed was set so that the torque was 10% to 90%, and the value when the viscosity stabilized was read 2 minutes after the start of the measurement.

[0269] [Determination of storage elastic modulus and glass transition temperature (Tg)]

[0270] The dynamic viscoelasticity measuring device (DMA: manufactured by UBM, trade name: E4000F) was used to measure the resin sheet of 5 mm×20 mm size from 30°C to 400°C at a heating rate of 4°C / min and a frequency of 11 Hz. The temperature at which the value of the elastic modulus change (Tanδ) during the measurement becomes the maximum is defined as Tg.

[0271] [Determination of relative dielectric constant and dielectric loss tangent]

[0272] The relative dielectric constant and dielectric loss tangent of the resin sheet at 10 GHz were measured using a vector network analyzer (manufactured by Agilent, trade name: E8363C) and a split post dielectric resonator (SPDR) resonator. The material used in the measurement was placed under the conditions of a temperature of 24°C to 26°C and a humidity of 45% to 55% RH for 24 hours.

[0273] [Determination of coefficient of thermal expansion (CTE)]

[0274] For a polyimide film of 3 mm × 20 mm size, a thermal mechanical analyzer (manufactured by Bruker, trade name: 4000SA) was used to apply a load of 5.0 g while raising the temperature from 30°C to 265°C at a certain heating rate, and then keep it at the temperature for 10 minutes, and then cool it at a rate of 5°C / min to determine the average thermal expansion coefficient (thermal expansion coefficient) in the longitudinal direction (Machine Direction, MD) from 250°C to 100°C.

[0275] [Measurement of dimensional change rate]

[0276] A metal-clad laminate of 80 mm x 80 mm size is prepared. A dry film resist is placed on the metal layer of the laminate, and then exposed and developed. Figure 4 As shown, 16 resist patterns with a diameter of 1 mm were formed so that five locations could be measured at intervals of 50 mm in the machine direction (MD) and the transverse direction (TD), thereby preparing a target for position measurement.

[0277] In an environment of temperature: 23±2°C and relative humidity: 50±5%, the distance between the targets of the resist pattern in the position measurement target is measured, and then the exposed part of the metal layer in the opening of the resist pattern is removed by etching (the temperature of the etching solution: below 40°C, the etching time: within 10 minutes), such as Figure 5 As shown in FIG. 1 , an evaluation sample having 16 metal layer residual points was prepared. The evaluation sample was left to stand for 24±4 hours in an environment of temperature: 23±2°C and relative humidity: 50±5%, and then the distance between the metal layer residual points was measured. The dimensional change rate of each of the five locations in the longitudinal and transverse directions relative to the normal state was calculated, and the dimensional change rate after etching was set based on the average value of each.

[0278] The evaluation sample was then heat treated in an oven at 120°C for 1 hour, and the distance between the metal layer remaining points was measured. The dimensional change rate after heating was calculated at five locations in the longitudinal and transverse directions, and the average value was used as the dimensional change rate after heating.

[0279] Each dimensional change rate was calculated according to the following formula.

[0280] Dimension change rate after etching (%) = (BA) / A×100

[0281] A: Distance between targets after resist development

[0282] B: The distance between the remaining points of the metal layer after etching

[0283] Dimensional change rate after heating (%) = (CB) / B×100

[0284] B: The distance between the remaining points of the metal layer after etching

[0285] C: The distance between the remaining points of the metal layer after heating

[0286] [Measurement of surface roughness of copper foil]

[0287] Determination of ten-point average roughness (Rz)

[0288] The surface roughness was determined using a stylus surface roughness meter (manufactured by Kosaka Laboratory Co., Ltd., trade name: Surfcorder ET-3000) under the measurement conditions of force: 100 μN, speed: 20 μm, and range: 800 μm. The surface roughness was calculated according to the method of Japanese Industrial Standards (JIS)-B0601:1994.

[0289] The abbreviations used in the synthesis examples represent the following compounds.

[0290] BTDA: 3,3',4,4'-Benzophenonetetracarboxylic dianhydride

[0291] PMDA: Pyromellitic Dianhydride

[0292] BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride

[0293] DAPE: 4,4'-diaminodiphenyl ether

[0294] m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl

[0295] TPE-R: 1,3-bis(4-aminophenoxy)benzene

[0296] DDA: C36 aliphatic diamine (manufactured by Croda Japan Co., Ltd., trade name: PRIAMINE 1074, amine value: 205 mgKOH / g, mixture of dimer diamines of cyclic structure and chain structure, content of dimer component: 95 wt % or more)

[0297] OP935: Aluminum salt of organic phosphinate (manufactured by Clariant Japan, trade name: Exolit OP935)

[0298] N-12: Dodecanedioic acid dihydrazide

[0299] DMAc: N,N-dimethylacetamide

[0300] NMP: N-methyl-2-pyrrolidone

[0301] (Synthesis example 1)

[0302] 312 g of DMAc was placed in a reaction container including a thermocouple and a stirrer and capable of introducing nitrogen. 14.67 g of DAPE (0.073 mol) was dissolved in the reaction container while stirring in the container. Then, 23.13 g of BTDA (0.072 mol) was added. Thereafter, stirring was continued for 3 hours to prepare a polyamic acid resin solution a having a solution viscosity of 2,960 mPa·s.

[0303] (Synthesis example 2)

[0304] 200 g of DMAc was placed in a reaction vessel including a thermocouple and a stirrer and capable of introducing nitrogen. 1.335 g of m-TB (0.0063 mole) and 10.414 g of TPE-R (0.0356 mole) were dissolved in the reaction vessel while stirring in the vessel. Then, 0.932 g of PMDA (0.0043 mole) and 11.319 g of BPDA (0.0385 mole) were added. Thereafter, stirring was continued for 2 hours to prepare a resin solution b of polyamic acid having a solution viscosity of 1,420 mPa·s.

[0305] (Synthesis example 3)

[0306] 250 g of DMAc was placed in a reaction vessel including a thermocouple and a stirrer and capable of introducing nitrogen. In the reaction vessel, 12.323 g of m-TB (0.0580 mole) and 1.886 g of TPE-R (0.0064 mole) were dissolved while stirring in the vessel. Then, 8.314 g of PMDA (0.0381 mole) and 7.477 g of BPDA (0.0254 mole) were added. Thereafter, stirring was continued for 3 hours to prepare a resin solution c of polyamic acid having a solution viscosity of 31,500 mPa·s.

[0307] (Synthesis Example 4)

[0308] 44.92g of BTDA (0.139 mol), 75.08g of DDA (0.141 mol), 168g of NMP and 112g of xylene were placed in a 500mL four-necked flask with a nitrogen inlet tube, a stirrer, a thermocouple, a Dean-Stark trap and a cooling tube, and mixed at 40°C for 30 minutes to prepare a polyamic acid solution. The polyamic acid solution was heated to 190°C and heated and stirred for 4 hours, and the distilled water and xylene were removed to the outside of the system. Thereafter, it was cooled to 100°C, 112g of xylene was added and stirred, and then cooled to 30°C, thereby completing imidization to obtain a resin solution d (solid content: 29.5% by weight) of polyimide.

[0309] (Production example 1)

[0310] <Preparation of polyimide film 1>

[0311] 1.8 g of N-12 (0.0036 mol) and 12.5 g of OP935 were mixed in 169.49 g of resin solution d (solid content: 50 g), and 6.485 g of NMP and 19.345 g of xylene were added for dilution to prepare a polyimide varnish 1.

[0312] The polyimide varnish 1 was applied to the silicone-treated surface of the release substrate so as to have a thickness of about 25 μm after drying, and then dried by heating at 80° C. and peeled from the release substrate to prepare a polyimide film 1. The polyimide film 1 had a Tg of 53° C., a storage elastic modulus of 800 MPa at 50° C., and a maximum storage elastic modulus of 10 MPa at 180° C. to 260° C.

[0313] (Production example 2)

[0314] <Preparation of polyimide film 2>

[0315] The resin solution b of polyamic acid is applied to one surface of an electrolytic copper foil 1 (thickness 12 μm, Rz: 2.1 μm) in such a manner that the thickness after curing becomes about 25 μm, and then the solvent is removed by heating and drying at 120°C. Furthermore, a stepwise heat treatment is performed from 120°C to 360°C to complete imidization. An aqueous solution of ferric chloride is used to etch and remove the copper foil to prepare a polyimide film 2. The Tg of the polyimide film 2 is 250°C, the storage elastic modulus at 50°C is 5000 MPa, and the maximum value of the storage elastic modulus at 180°C to 260°C is 3600 MPa.

[0316] (Production example 3)

[0317] <Preparation of resin film 1>

[0318] The polyimide varnish 1 was applied to the surface of the LCP film 1 (50 μm thick, CTE: 29 ppm / K, manufactured by Kuraray Co., Ltd., trade name: Vecstar) so that the thickness after drying was about 5 μm, and then heated and dried at 80° C. Then, the polyimide varnish 1 was also applied to the surface on the opposite side of the LCP film 1 so that the thickness after drying was about 5 μm, and then heated and dried at 80° C. to prepare a resin film 1. The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the resin film 1 were 2.9 and 0.0021, respectively.

[0319] (Production example 4)

[0320] <Preparation of resin film 2>

[0321] The resin solution b is applied to the surface of the LCP film 1 in such a manner that the thickness after curing becomes about 5 μm, and then heated and dried at 120°C. Subsequently, the resin solution b is also applied to the surface on the opposite side of the LCP film 1 in such a manner that the thickness after curing becomes about 5 μm, and then heated and dried at 120°C to remove the solvent. In the above manner, three polyamic acid layers are formed, and then a step-by-step heat treatment is performed from 120°C to 260°C to complete imidization, thereby preparing a resin film 2. The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the resin film 2 are 3.1 and 0.0021, respectively.

[0322] (Production example 5)

[0323] <Preparation of resin film 3>

[0324] A resin film 3 was prepared in the same manner as in Production Example 3 except that the thickness of the polyimide varnish 1 after drying was about 12.5 μm. The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the resin film 3 were 2.8 and 0.0021, respectively.

[0325] (Production example 6)

[0326] <Preparation of resin film 4>

[0327] A resin film 4 was prepared in the same manner as in Production Example 3 except that the thickness of the polyimide varnish 1 after drying was about 25 μm. The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the resin film 4 were 2.8 and 0.0022, respectively.

[0328] (Production example 7)

[0329] <Production of single-sided metal-clad laminate 1>

[0330] Resin solution b is uniformly applied to a single surface of the electrolytic copper foil 1 so that the thickness after curing becomes about 2 μm, and then heated and dried at 120°C to remove the solvent. Subsequently, resin solution c is uniformly applied to the resultant so that the thickness after curing becomes about 21 μm, and then heated and dried at 90°C to 120°C to remove the solvent. Furthermore, resin solution a is uniformly applied to the resultant so that the thickness after curing becomes about 2 μm, and then heated and dried at 120°C to remove the solvent. Three layers of polyamic acid layers are formed in the above manner, and then staged heat treatment is performed at 120°C to 360°C to complete imidization, thereby producing a single-sided metal-clad laminate 1. The CTE of the polyimide film 3 prepared by etching and removing the copper foil layer of the single-sided metal-clad laminate 1 using an aqueous solution of ferric chloride is 23ppm / K.

[0331] (Production example 8)

[0332] <Production of single-sided metal-clad laminate 2>

[0333] Resin solution b is evenly applied to a single surface of the electrolytic copper foil 1 so that the thickness after curing becomes about 2 μm, and then heated and dried at 120°C to remove the solvent. Subsequently, resin solution c is evenly applied to the resultant so that the thickness after curing becomes about 21 μm, and then heated and dried at 90°C to 120°C to remove the solvent. Furthermore, resin solution b is evenly applied to the resultant so that the thickness after curing becomes about 2 μm, and then heated and dried at 120°C to remove the solvent. Three layers of polyamic acid layers are formed in the above manner, and then staged heat treatment is performed at 120°C to 360°C to complete imidization, thereby producing a single-sided metal-clad laminate 2. The CTE of the polyimide film 4 prepared by etching and removing the copper foil layer of the single-sided metal-clad laminate 2 using an aqueous solution of ferric chloride is 22ppm / K.

[0334] (Production example 9)

[0335] <Production of Single-Sided Metal-Clad Laminated Plate 3>

[0336] Electrolytic copper foil 1 was laminated on the resin side of single-sided metal-clad laminate 2, and then hot-pressed for 30 minutes at 320°C and 7MPa to produce double-sided metal-clad laminate 1. The copper foil layer on one side of double-sided metal-clad laminate 1 was etched away using an aqueous ferric chloride solution to produce single-sided metal-clad laminate 3 having a roughened shape of copper foil transferred to the resin surface. The CTE of polyimide film 5 prepared by etching away the copper foil layer of single-sided metal-clad laminate 3 using an aqueous ferric chloride solution was 22ppm / K.

[0337] [Example 1]

[0338] Two single-sided metal-clad laminates 1 and one resin film 1 were prepared, and the laminates were stacked in the order of single-sided metal-clad laminate 1 / resin film 1 / single-sided metal-clad laminate 1, and then heat-pressed for 60 minutes at 180° C. and 3.5 MPa to prepare a double-sided metal-clad laminate 2. The results of the evaluation of the double-sided metal-clad laminate 2 are as follows.

[0339] Dimensional change rate after etching in MD direction: -0.04%

[0340] Dimension change rate after etching in TD direction: -0.03%

[0341] Dimensional change rate after heating in MD direction: +0.02%

[0342] Dimensional change rate after heating in TD direction: +0.01%

[0343] The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the resin laminate 1 (thickness: 110 μm) prepared by etching away the copper foil layers on both sides of the double-sided metal-clad laminate 2 were 3.1 and 0.0031, respectively.

[0344] [Example 2]

[0345] Two single-sided metal-clad laminates 2 and one resin film 1 were prepared, and the laminates were stacked in the order of single-sided metal-clad laminate 2 / resin film 1 / single-sided metal-clad laminate 2, and then heat-pressed for 60 minutes at 180° C. and 3.5 MPa to prepare a double-sided metal-clad laminate 3. The results of the evaluation of the double-sided metal-clad laminate 3 are as follows.

[0346] Dimensional change rate after etching in MD direction: -0.05%

[0347] Dimension change rate after etching in TD direction: -0.03%

[0348] Dimensional change rate after heating in MD direction: -0.03%

[0349] Dimensional change rate after heating in TD direction: ±0.00%

[0350] The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the resin laminate 2 (thickness: 110 μm) prepared by etching away the copper foil layers on both sides of the double-sided metal-clad laminate 3 were 3.1 and 0.0026, respectively.

[0351] [Comparative Example 1]

[0352] Two single-sided metal-clad laminates 1 and one resin film 2 were prepared, and the laminates were stacked in the order of single-sided metal-clad laminate 1 / resin film 2 / single-sided metal-clad laminate 1, and then heat-pressed for 30 minutes at 320° C. and 7 MPa to prepare a double-sided metal-clad laminate 4. The results of the evaluation of the double-sided metal-clad laminate 4 are as follows.

[0353] Dimensional change rate after etching in MD direction: -0.03%

[0354] Dimension change rate after etching in TD direction: -0.01%

[0355] Dimensional change rate after heating in MD direction: -0.11%

[0356] Dimensional change rate after heating in TD direction: -0.10%

[0357] The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the resin laminate 3 (thickness: 110 μm) prepared by etching away the copper foil layers on both sides of the double-sided metal-clad laminate 4 were 3.2 and 0.0031, respectively.

[0358] [Example 3]

[0359] Two single-sided metal-clad laminates 2 and one resin film 3 were prepared, and the laminates were stacked in the order of single-sided metal-clad laminate 2 / resin film 3 / single-sided metal-clad laminate 2, and then heat-pressed for 60 minutes at 180° C. and 3.5 MPa to prepare a double-sided metal-clad laminate 5. The results of the evaluation of the double-sided metal-clad laminate 5 are as follows.

[0360] Dimensional change rate after etching in MD direction: -0.06%

[0361] Dimension change rate after etching in TD direction: -0.05%

[0362] Dimensional change rate after heating in MD direction: +0.04%

[0363] Dimensional change rate after heating in TD direction: +0.02%

[0364] The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the resin laminate 4 (thickness: 125 μm) prepared by etching away the copper foil layers on both sides of the double-sided metal-clad laminate 5 were 3.0 and 0.0026, respectively.

[0365] [Example 4]

[0366] Two single-sided metal-clad laminates 2 and one resin film 4 were prepared, and the laminates were stacked in the order of single-sided metal-clad laminate 2 / resin film 4 / single-sided metal-clad laminate 2, and then heat-pressed for 60 minutes at 180° C. and 3.5 MPa to prepare a double-sided metal-clad laminate 6. The results of the evaluation of the double-sided metal-clad laminate 6 are as follows.

[0367] Dimensional change rate after etching in MD direction: -0.05%

[0368] Dimension change rate after etching in TD direction: -0.04%

[0369] Dimensional change rate after heating in MD direction: +0.01%

[0370] Dimensional change rate after heating in TD direction: +0.01%

[0371] The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the resin laminate 5 (thickness: 150 μm) prepared by etching away the copper foil layers on both sides of the double-sided metal-clad laminate 6 were 3.0 and 0.0026, respectively.

[0372] [Comparative Example 2]

[0373] Two single-sided metal-clad laminates 2 and a LCP film 1 were prepared and stacked in the order of single-sided metal-clad laminate 2 / LCP film 1 / single-sided metal-clad laminate 2, and then hot-pressed at 305°C and 7MPa for 30 minutes. However, the bonding between the resin surface of the single-sided metal-clad laminate 2 and the surface of the LCP film 1 was insufficient, and a double-sided metal-clad laminate could not be obtained.

[0374] [Comparative Example 3]

[0375] Two single-sided metal-clad laminates 3 and one LCP film 1 were prepared, and the laminates were stacked in the order of single-sided metal-clad laminate 3 / LCP film 1 / single-sided metal-clad laminate 3, and then heat-pressed at 305° C. and 7 MPa for 30 minutes to prepare a double-sided metal-clad laminate 7. The results of the evaluation of the double-sided metal-clad laminate 7 are as follows.

[0376] Dimensional change rate after etching in MD direction: -0.04%

[0377] Dimension change rate after etching in TD direction: -0.03%

[0378] Dimensional change rate after heating in MD direction: -0.12%

[0379] Dimensional change rate after heating in TD direction: -0.12%

[0380] The relative dielectric constant (Dk) and dielectric loss tangent (Df) of the resin laminate 6 (thickness: 100 μm) prepared by etching away the copper foil layers on both sides of the double-sided metal-clad laminate 7 were 3.2 and 0.0027, respectively.

[0381] As mentioned above, although embodiment of this invention was described in detail for the purpose of illustration, this invention is not limited to the said embodiment, Various deformation|transformation is possible.

Claims

1. A resin film, characterized in that include: a liquid crystal polymer layer; a first adhesive layer laminated on one side of the liquid crystal polymer layer; as well as The second adhesive layer is laminated on the side of the liquid crystal polymer layer opposite to the first adhesive layer, wherein The storage elastic modulus of the first adhesive layer and the second adhesive layer at 50° C. is independently 1800 MPa or less, and the maximum value of the storage elastic modulus at 180° C. to 260° C. is independently 800 MPa or less. The first adhesive layer and the second adhesive layer contain polyimide as a resin component.

2. The resin film according to claim 1, wherein The dielectric loss tangent of the entire resin film at 10 GHz is 0.005 or less.

3. The resin film according to claim 1, wherein The glass transition temperatures of the first adhesive layer and the second adhesive layer are each 180° C. or lower.

4. The resin film according to claim 1, wherein The polyimide contains an acid anhydride residue derived from a tetracarboxylic anhydride component and a diamine residue derived from a diamine component, and contains 50 mol % or more of diamine residues derived from a diamine derived from a dimer acid in which both terminal carboxylic acid groups of a dimer acid are substituted with a primary aminomethyl group or an amino group, based on all the diamine residues.

5. The resin film according to claim 1, wherein When the thickness of the liquid crystal polymer layer is set to TL, the thickness of the first adhesive layer is set to TB1, and the thickness of the second adhesive layer is set to TB2, the following relationship exists; 0.15≦(TB1+TB2) / (TL+TB1+TB2)≦0.

70.

6. A metal-clad laminate, characterized in that: include: A first single-sided metal-clad laminate having a first metal layer and a first insulating resin layer laminated on at least one side of the first metal layer; a second single-sided metal-clad laminate having a second metal layer and a second insulating resin layer laminated on at least one side of the second metal layer; and The intermediate resin layer is arranged in contact with the first insulating resin layer and the second insulating resin layer and is laminated between the first single-sided metal-clad laminate and the second single-sided metal-clad laminate, wherein: The intermediate resin layer includes the resin film according to any one of claims 1 to 5 .

7. The metal-clad laminate according to claim 6, wherein: The total thickness T1 of the first insulating resin layer, the intermediate resin layer and the second insulating resin layer is within a range of 50 μm to 500 μm, and the ratio of the thickness T2 of the intermediate resin layer to the total thickness T1, ie, T2 / T1, is within a range of 0.50 to 0.

90.

8. The metal-clad laminate according to claim 6, wherein: The first insulating resin layer and the second insulating resin layer each have a multilayer structure in which a thermoplastic polyimide layer, a non-thermoplastic polyimide layer and a thermoplastic polyimide layer are sequentially stacked. The intermediate resin layer is disposed in contact with the two thermoplastic polyimide layers.

9. The metal-clad laminate according to claim 8, wherein: The non-thermoplastic polyimide constituting the non-thermoplastic polyimide layer comprises a tetracarboxylic acid residue and a diamine residue, and the content of the diamine residue derived from the diamine compound represented by the following general formula (A1) is 80 parts by mole or more relative to 100 parts by mole of all diamine residues; In formula (A1), the linking group Z represents a single bond or -COO-, Y independently represents a monovalent hydrocarbon group having 1 to 3 carbon atoms which may be substituted by a halogen atom or a phenyl group, or an alkoxy group having 1 to 3 carbon atoms or a perfluoroalkyl or alkenyl group having 1 to 3 carbon atoms, n represents an integer of 0 to 2, and p and q independently represent an integer of 0 to 4.

10. A circuit substrate, characterized in that: include: A first circuit substrate including a first wiring layer and a first insulating resin layer laminated on at least one side of the first wiring layer; a second circuit substrate including a second wiring layer and a second insulating resin layer laminated on at least one side of the second wiring layer; and The intermediate resin layer is arranged in contact with the first insulating resin layer and the second insulating resin layer and is stacked between the first circuit substrate and the second circuit substrate, wherein: The intermediate resin layer includes the resin film according to any one of claims 1 to 5 .

Citation Information

Patent Citations

  • Polyimide resin-liquid crystal polymer composite film and method of producing the same

    JP2015074157A

  • Three-layer film, method of producing three-layer film, laminate and printed circuit board

    JP2016117281A

  • Metal coated lamination plate, adhesion sheet, adhesive polyimide resin composition, and circuit substrate

    CN110871606A

  • Resin composite material, and beam structure member using the same

    JP2011011346A